T-UNIT SEBAGAI ALAT UKUR KEMAMPUAN MENGARANG BAHASA INDONESIA - Ghazali, Syukur (LITERA, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAkgAAAG1CAIAAACNmJyiAAAgAElEQVR4nOydeTxV2///NyJFgwap0IAiNKk03TIUQiqVEkWGkkRCZpJ5uJWESIYMGUIkknmehwyFzMMxT8dxHGfY+/fHetz9OF+q272f4X7y288/PJy911577Wm91vu93mstCMHAwMDAwFhAQP90ATAwMDAwMP6dYMKGgYGBgbGgwIQNAwMDA2NBgQkbBgYGBsaCAhM2DAwMDIwFBSZsGBgYGBgLCkzYMDAwMDAWFJiwYWBgYGAsKDBhw8DAwMBYUGDChoGBgYGxoMCEDQMDAwNjQYEJGwYGBgbGggITNgwMDAyMBQUmbBgYGBgYCwpM2DAwMDAwFhSYsGFgYGBgLCgWmrDBMEwmk2dmZmZmZmZnZykUyuzsLPhJoVBgGKZPCcMwhUIhk8kgGY1GQzfOzs6Cw6lUKvgHHAv/AY1GI5PJZDKZSqXCMAyS0Wg0cMicBDQajUql0qenLwmASqWSSCRQbBqNBs5FoVAoFAqNRgM5oz/BGclkMv0ucBRayJ+5V/RnB7cCLeGcBOj/aOb0W8AFosVGS/KTj4y+wDAdP3ns/Mv55s/5ef7MiX6mJD9T1G8W+JsH/vhCfj7zv13I+Yf85OP4Syf63hP5XiY/+aDn5D///7/KXz3vDwrwzfL8IJ8fv67fy+QHFwuqju+d92/fov9BFpqwffjwYd++fSIiIiIiIrt37967d+/OnTvBz5s3b7a0tNAnHh0ddXd337179549e2RlZauqqsD2uLi4Y8eOiYmJhYWFVVVVaWpqysvLOzs7DwwMoMfW1dXdvHnz7NmzYWFhFAolNTVVXFzczMzMzs4uJyeHQCD8/vvvBgYG9+7dMzU1tbCwMDc3NzExMTQ0dHR0LC8vn1PsxsZGa2vrgwcP7tmz5/z58/7+/kNDQ6Ojo4GBgWZmZmZmZvfv3zc1NTUxMbl7966bm1t3d3dJSYm+vr65uTnI2dTU9NGjR1VVVRQKBfm/72hbW1t4eHh1dfWck6JpiouLzc3N7927B/K3tLSMjY0dGBiY86JPTU3h8fh3794FBQXNyerLly8uLi729vZv3rwpKSmhv1FzaG9vr6mpGR8fp9+Ix+MrKioyMzMzMjKysrKmpqaQb31mVCq1ra2tpKSESqXSXwKBQKisrExNTQWHZ2VlZWRkfPjwIScnp7+/H6aT4b6+vvz8/PT09Pz8/M7OTpAJiURqamoik8no7RobG6NQKP39/RMTE/MvYX7B6OuLbyaYkxhN9s2Uc5oFP2glfLMk39v1MzXpXy3qvwJok/1A2L65a3Z2dnh4mP6e/Iww/NXy/0zi+YX/cT706b/3/5/m9gNh+5k3EP6Ljc5fl4UmbM7OzlxcXG/evAkJCREXF4cg6OrVq69fv37z5o2hoWFWVhaaEoZhEon08eNHfn5+CIJu3brV19cHdrW3t1+/fl1LS6ulpWVkZOTly5dcXFwrV668c+fO7OwsSDM2NvbixQstLa03b97QaLTu7m49Pb2lS5fKy8v39PRMT0+fPXv25cuXaWlply9fXrZs2b59+yIjI9++fauurv7gwQP616uhoUFBQUFSUtLZ2TkhIcHJyUlCQiIgIIBEItXW1t6+fZuDg0NYWNjc3NzT09Pc3PzcuXOJiYmDg4Pe3t4bN25cv379zZs3LS0td+zYISoqmpqaOufdDQ0N5ebmVlNTm3+7uru779y5IyQkpKqq6urq+vz586ioKG1tbSkpKRsbmznVekFBwbNnz5SUlI4cOdLc3Ey/q7293cLCYtOmTTt27Hjx4gWRSPzeA7p79+7OnTtTUlLoNxKJxIiICDExMWFhYScnJ3De+R9nZ2fn1atXjx8/3tDQQL89OjpaSUnp4sWLMjIy27ZtExISkpCQUFVVlZeXt7KyGhsbQ1MWFxdfu3Zt27ZtwsLCDx48wOPxCIJMTEwYGRlJSUnZ2dlVVFQ4ODhISEhISEicPHkyJiYGQRASiRQYGPjbb7/p6uoWFxenpKTo6OhISEjIyspaWVk1NjbCMDw4OPjo0SNFRUVNTc3i4uKAgAB5eXlpaemjR4+Ki4sfOnRIW1u7oKCATCbPqexSU1M1NTVBbtbW1l++fEEQZGBgwMLC4siRI15eXpOTk0FBQbKystLS0seOHRMXFxcXFz9y5IiDg0NeXt6NGzckJCTk5eVDQ0NJJBJ95pWVlTdv3pSWlpaSknry5An9Hfv69au6unpERAT9q0Imk8PDw48ePaqqqvr48eP5rZOvX7/6+/vb29u7u7unpqYWFRU9fPjQ0dHR2dnZ3t7exsbm999///TpE4IghYWFJiYmLi4u1tbW3t7eoNEAw3Bqaqqzs7OpqWlFRQWoZEGBOzs7vb29m5ub6cvf399vaWmprq7+6tWr3t5esJFKpba0tERGRj58+NDGxiYjIwN92SYnJ+Pi4iwsLGxtbYODg+e/e58+ffL29razs/v9999BA8ja2trJycnZ2dnOzs7W1tbGxsbGxqasrKy6utrDw8PBweHjx49oK4pGo9XX17u7u9vY2ERHRw8NDaE59/X1eXh4WFtbW1tb29nZ+fr65ubmonUF8ofwTE1N1dbWznl7YRju6OgoKSlJS0tLSEhIS0vLy8srKyubf//BzSGRSA0NDe3t7QjdN0Kj0QYGBoqLiwsLC0kkEnoIiUT6/PlzdnZ2aWlpa2sr/eOmUqn19fWPHj0KCgoqKChobGxEr3QBsNCE7fPnz0VFRQiCUKlUPT295cuXo694V1fX/HdlaGhIQUGBnZ09JCSE/rm+ePEiPDwc/F9RUbF48WIIgpYsWeLm5oY27T99+hQaGlpfXw9+pqenQxCkoaGBIAiNRgsPDx8ZGUEQxN3dnYGB4fjx411dXQiC5OXlxcbG0p/r8ePHEAS5u7uD17S7u9vc3Nzb2xvs9fX1ZWFhOXToUFVV1ejo6MDAQFZWVl1dHSgYDw8PJydnXFxcd3e3lZUVBEG2trYEAgH546Wvq6uTlpaGIIifn//z58/0106j0e7duwdB0OXLl+vq6oaHh6empigUSn19vb29/dmzZ1GlB4BGw+LFi5cuXeru7k6/i0wmp6Sk8PDwLF++PD4+/ntPp7+/X1hYGIIgCwsL1CwDVFRUbN++nYWFJS8vDxidKGhrtKCggIWFBYKgBw8egOoMbLewsDA1Nc3OznZxcVm8ePHKlStdXV1zcnIiIyPPnz/f0dFB/7jd3NyYmJi4uLgiIiJAFTA7O/vu3bulS5f6+Pj09fWVlZUdPnwYgiAZGZmmpiYKhRISErJ58+arV68mJiZ2d3c3Nze7u7uzsbExMjK6u7uDCo5AIERGRu7bt8/c3Ly7u7uyslJSUhKCoJMnTwYGBhoYGKxfv/7gwYOJiYlzLq2lpcXFxWXJkiWLFi3y8PAYGRkhkUgeHh67du3y8vIqKioikUgVFRW//fYbBEEHDhzw8vIKCAi4ePHiuXPnqqurAwICNmzYAEGQkJAQqOzQ2wLeKwiCtm3bVlJSgp6USqW+ePFi0aJF58+fx+Fw9O9DSUnJyZMnIQhat26dr6/vzMwMfWk9PT3Xr1+/cuVKbW3tlpaWjo4OKyur1atXL1u27ObNmzdv3ty2bduBAwc+fvzY1dVlZ2e3cuVKERER+pZWS0vLxYsXVVRUwFcDyjkzM+Pr68vLy+vv749+XEAGMjMzpaWlN23adOfOHVRI8Hh8YWHhyZMn79y509DQgL4toMa/e/cuGxubgIBAYmLinBaesbExJyfn6tWrzczM2tvb29vbXV1dV6xYwcnJaWxs/PDhQzs7ux07dnh7e+NwuOfPn+/atWvHjh3u7u6oF6S3t/fWrVu7du2KiYmZnp5GEGR6evrp06cHDhyQlZW1s7Ozs7OztrZWU1M7fvx4VFQUKrrgSquqqiQlJVVVVUGLCqWurs7BweHgwYObN2++du2atbX1b7/9JicnFxkZOd/AKi8vl5eXt7e3n/MiNTc33717d+/evffu3RscHET+6MtoaWm5ffu2rKxseXk5esPDwsJkZWWvXr1qa2vr6upqaWl58uRJHR2dOQ3WX5eFJmwoOBxOWVmZnZ19/vdJT09Pj4yMDBsbm5+fH30L6+nTpwEBAeD/jIyMI0eOPHjwgIWFhYODw8PDA1TK5eXlrq6uubm5IFlMTAwTE5O+vj7Ih0AgAPUKCAhYunSprKxsa2srSDk1NYVW1jAMgxrw4cOH6Os+NDQEHGWzs7MvXrxYtmyZvLw8OOnExMT4+Dg4tqysTFhYeMuWLaCZ7OnpycfHl5CQMDs7i+YfFBQkJCS0f/9+dnb2OR9DdnY2Nzf31q1bi4uL59yWoaGh/Px8cEbA8PCwrq4uKyvrsmXLIAiSk5ND6yBASUmJkJAQDw8PvVlMD41Gc3V15eXlhSBo9+7dpaWlCJ0fBofDnThxYv369fQGFgowr729vUFNvXPnzsnJSfTwiooKoMHV1dXCwsKCgoKVlZXgwKKiojmVSFpaGicnp5iYWG1tLbpxenp6+/btqIvY0NAQgiArKysEQQoKCsTExPT19elb6J8+fdq5cyc3N3dOTg66sampSUdHJz09Hfy0tLRkYmLy8vJCEKS3t/f48ePgKc+/utraWmFhYR4eHnBPvL29T548GRcXR5/G3NyciYkJPXxkZKSqqopMJnd2dh44cACCIAYGBnphGB0dvXDhAgRBy5cvn3NSGIbBrrVr1759+5Z+1+zsrJubG7jJIiIibW1t6K6WlhYJCQnQvHNycgIbQ0JCmJiYVq1alZOT8+XLl0OHDkEQZGBggCDIhw8fIAgSExObc7EmJiY2Njb0Tcz29nYlJSUIgo4dO0ZvbSAIMjExoaysDEHQ4sWLjY2NURkmEAgaGhrf/LRjYmJA+ZWUlOjfpbKyMkFBQQiCODg4UF96WVkZBEGsrKwVFRX9/f04HO7p06fZ2dkIgrS1tQGN5+bmTkpKQm9daGiogoJCRUUFgiDj4+Nubm6cnJzS0tKZmZl9fX29vb3d3d25ubm3b992c3Pr7+9HC0Cj0UBTg4uLKy8vj942nZiYePPmzaZNm3h5ecPDw4uLi2/fvg1B0KFDh+bcEARB7OzsIAiSlJREfemA8fFxDw8PRkZGZmbmu3fv9vT0oM/Uz89PWVl5dHQUQZCxsTELCws+Pj45ObmoqKi2trbW1tbCwkIrK6vTp0+jb++vzoIVNlSx0Lf/m37n7u7uPxW27Ozs27dvIwji7OwMPuP3798jCPLp0yczMzO0aggJCWFkZLx169acd9HPz2/JkiUyMjJfv35FN9ILm66uLgMDAycnp7Kysrm5eUhICH33T2Bg4LJlywQFBd3c3IKCglRUVBISEsDejIyMdevWsbOzKyoqXr16lY+Pz8XFBc0fQRAqlWpra6ulpRUQEABqGfoWuouLCzMz87Vr1+ir7DmgNy08PPzWrVtubm7m5ubbt2/n5eXNycmhv6UFBQWCgoLc3NwfP378Zlajo6NHjx61tbUF9pCHhwd9HE1XV5eUlNTq1atB5T6f6upqdXV1eXn5jRs3srOzp6eng4ge+iZtY2OjpKQkPz8/2tqYT2JiIgcHh4SEBP2tGBoaEhAQyM/PBz/19PQgCLK3t//y5YuBgcHjx4/n3KLi4mJhYeH169enpqaiG2tra69du4baZCYmJkxMTKampuDaZWVlN23a9OHDh/lFKiwsFBQU3Lp1a1paWmxs7JkzZ6KiosAucHMoFIqRkREDA8PLly/B9oGBAdC4zs/PFxISAooiKiqK9hMHBARISkpu3rx59erVL168QM9FpVLLysr27t27fv16CILu3r1L3985OzsbHBy8detWQUFBJiYmJycnYP0jCGJlZcXJybl27VoODo7ff/8dQRAymfz8+XM2NjZJSUmQTF1dHYKgmzdvIggSHR0NQdD+/fvnaI+tra2dnR3qWkQQJCsra926dXx8fCtWrMjJyaHvQB0YGLh169bmzZvXrl27ePFiNzc3sGt8fPz27ds+Pj7zO0FjY2MXLVrEycm5cePGmJgYNLcbN25s3bp1/fr169atQ50xVVVVEAStXr0a/WZHR0eBKQbs0S1btoCrAG81DMM5OTna2tqgDZSSkrJ27Vo+Pj6gc/TgcLjGxsbJyUn0G+nv77e2tt6wYQMLC4u+vj591y94jtu2bVNQUABaWFRUBEEQHx/fHK9+R0eHuro6IyPjmjVr5nR1wzCclpYmIiICQRAjI+PTp0/RzN+9e6eqqgoeWUhIyLJly8TFxUFrGGV0dDQvL6+zs/M/0Z/632fBCltvb6+cnNwcYQOGSGJiYmJiYm5u7sTExPeEzdfXF31vcnJygINxdnYWtOWPHj1aVFTU0NBgamr6+vVrBEGoVOqTJ0/ohQ19OeYIG0wHSNDc3GxsbHzo0CFOTk4IgpiYmM6dO5eRkYEgCJlMfvHiBRsbGxcX14MHD/z8/Dg5OdHP+/Xr1wwMDOzs7CdOnFBVVRUSEjIwMMjIyCAQCCDziooKExOT0tLSzs5OHh6eZcuWvXjxAlUC0PRzcHBArxrEdtLfRtR3oa+v7+PjA4rk4uKyaNGiOZ12PxY2KpVaUFCgpqY2Njb2+vVrDg4OBQUF4CSkFzYODo7MzMxvPtDXr19ramr29vba29svXbr06tWrwGhD6FoJ1dXVBw4coBe2+Z8oEDZJSUn61jS9sNFotOvXr4OnfOLEiePHj885C/Jzwqavr8/IyGhkZJSenm5sbKysrBwdHU0kEucXqaioaMeOHRwcHHJycvz8/EALETpzlkKh3L17l4WFRVFR0dLS0tzcXF1dPTAwEEGQ/Px8RUXFx48fb9q0CYIgNze3mZkZGo0mLy9vampqZGTEzMz86NEj9Fx4PF5XV/fevXsvX77cvn37jh07ysrK6AtTXFysoqLy+PHjpUuXcnNzg729vb2XLl06c+aMnJzckiVLPD09EQSZnZ0NCAhgZ2cXERHx9/d/9eqVoKCgiIhIWloagiAhISEQBAkLC4NeQxRra2tbW1tU2CYnJ589eyYvL+/i4sLCwnLx4kXUkQ6u3d/f38rKysXFhYmJaePGjWFhYQiCEAiEW7dufVPYQkND+fn579+/D0GQvLw86A6or6+XlZXV09OTkpJavnw5yAT5Q9iWLl0aFBQUHx/v4+OTmpoK3qvPnz8HBQU9fvz4zJkzEAQdOXKku7sb3AoDAwPQ/LK0tIQgSFNTE3w1oJn1vUii+Pj4+/fvP336lI2NTVBQELx+6GU+e/ZsyZIlaIF///33FStW2Nvbz3HLP3nyxNbWVldXd8mSJadPn6ZvH5DJ5Hfv3llbW5uZmXFzc2/bti06OhocHhQUtH//fvD01dTUWFhYvLy80I5PUAAQEY383/f81+X/I2FDECQnJ+fy5cv79u3bvXu3rq7uwMBAT0/PyZMn2djYAgMD6X1rTk5OHh4e4P/379+fOHECvLu9vb3ANyIlJeXu7q6pqRkZGYkgCIVC8ff3Z2Ji+kmLbQ6zs7M1NTXx8fGWlpZiYmIQBF26dAlkGxgYyMbGduDAAeC9efXqFeo5DA0NBT0ooMstISGBhYWFn5+/pqYGJHB0dBQTE7O1tTU1NQWqKSkpCTwS4BoXLVqkr6+PttmHh4ejo6Pd3NyCg4MjIyNRT1RhYaG4uPiZM2eePHny9OnT8+fPQxC0adOmr1+/ot/Aj4WNSCRevXr18OHD4Mvk4OBYu3ZtdHQ0mgC12Ob7RREEmZiYsLCwOHXqVH5+vouLCzj7nBoTQZD09HQuLq5t27bl5eV971YnJiauWbNm165d9BX60NAQHx8fELbZ2dlLly5BELRy5UoODg4eHp4XL16gNRdIX1ZWJioqumHDBlCJA+iFjUajnT59GoIga2trbW1tCIKuXbsGkn1T2ERERJiZmdnY2CAIunDhAuiORasYIGysrKy8vLwyMjKKiopiYmJPnz5FEKS6ulpPTy86OtrCwoKVlXX//v3t7e05OTlKSkplZWVPnz6FIMjIyAg915cvX/j5+V+/fj08PAzsvDkN/4qKiuvXrzc0NOzYsQOCIENDQxiG/f39TUxMsrKy1NXVWVhYUGHz9fVlZ2fn4+PT0dG5cuWKurr6+/fvQZnDwsKAz3lOTy2IsEAdZXl5edeuXSsqKurq6uLi4lq9enVVVRV93ern5xcRETE8PKynp7do0aINGzZER0ePjIwYGRl9U9gCAwMlJSXr6+t5eXnXrFkDvIiGhoYWFhZZWVkyMjLLli2bI2wMDAynT5/W1tY+duyYtbU1MOUbGxuDg4Pr6+tbWlpAL7Wenh44nbm5OejIv3nzJgRBxsbG6Nm/JwkwDHt6eoK+ACMjIw4OjtDQUGBNgkOio6PXr18vKSkZHR3t6OgoIyNjbW0NXKlonkQiUUtLKz4+fmpqSk5ODmSCngIIm7+//8DAQGBg4JIlS/j5+YE/KTk5+erVqwiCTExMnD9/npWVNSIi4ntF/fkozf9lFqyw9ff3y8vLs7Ozg/BCsLG6uvrp06dOTk729vZRUVFUKrWnp0dWVpaVlZW+VYsgyI0bN9CGc1pampSUFJrJ58+flZSUmJmZ161bd+7cObRbPjMzk5GR8fbt23M6nwICApYsWULfx0YPDMOlpaWowwdBkPfv3y9fvhwYCkDY2NnZZWRk6C0M0BCLjIykbxRTqVReXl5GRkZgr5BIpDt37uzYseP48eMSEhLHjh1bsWIFBwdHXl4eMNpSUlLWr1+/ceNG1LE+ODj47Nkz0LUAQRC63cjISFBQUFpa+rfffvvtt9/279+/YsWKZcuWPXz4EHX1/EDYQIgEPz//kSNHrl+/rqmpKSoqCnxWqNXV1dV18uTJlStXxsbGojbl7OwsuO0pKSl79+6Vk5PT0dG5dOnS8uXLGRgYnJ2dgdcIBZg+AgICfypsYmJi9OMf8Hi8kJAQEDYKhXL16lUQB+Th4cHAwMDBwQGaLyipqalbt27l4eEBhjWgvr5eU1PzzZs3CILQaLSzZ88yMDCYm5v7+/tv2LBBSEjoe8ZoYWGhkJAQFxeXjY3N2bNnIQjS0dFBq37kD1ckcGyCR5+WlgYiSysrKzU0NNLS0srLyzk4OCAI8vLyQoMLnJ2dIQi6ePEiyIdEIvn7+69Zs+b27duPHj3avn07BEFnzpyh70srLi5WVlYeGhry8vJiYWFZtWpVeHi4mpra8+fPR0ZGlJWVUWGjUqkxMTErVqyQlZUtKSmpra2lfxyg1SUmJjan09Te3t7R0RG8zGQy2c3Nbe3atY6Ojo8ePeLi4mJiYkIDiwC+vr7Pnj1DEASHwwFLmpeXNyoqSkdHx9fXd76wBQQEHD16lEAgODk5QRB04sQJcEVv377t6Og4duzYfGFjZWV99epVaWlpcHBwdHT08PAwgiCNjY1BQUHAMqutreXj44MgyNXVFYfD3b9/H3z1oCcM9CkCyGTyp0+fYmNj3759m5CQgH6zjY2NKioqampqaWlpFhYWIKqI3gnc0NAAomfv3bvHwcHBxcUVGxsLdqGfQ0lJyfHjx83NzZOSkoA/X1dXF3WxUCiUpKQkBweHjo4OCoViZmbGzMy8a9eupqamiooKa2trBEHGx8fPnDmzePFi+li54eHh3NzchISE5ORkEGCCCdv/KDAMNzY2HjlyBIIgOzu7742LQhBkbGzM3NyckZFRUlIyPT398+fPjY2N8fHxIMgYpPnw4YOWlha99nz58uXo0aMQBCkrK4PGNYidA5UIWlkjCEImk93d3UHH+HwLAxy4Z88eLy+voaEhPB4/Pj7+/Plzbm5u0Awkk8m+vr6srKxHjx6tr6/H4/EEAiEpKamgoABBkHfv3jEyMm7atCkvL29kZCQuLm7lypUXLlwAPpOUlBQjIyPUKTc0NHT27FlgogHH/ezsrI6ODgMDg5qaGv0Iv4qKCiBs4NImJiZOnDiB2q8IgoyMjBgbGwP/DKgFwFHbtm1bv349fV2PejkeP358//59tI5LTk7m5uYWEBBA+5y6u7slJSXZ2dnR206lUrOyskDBnJ2dJSUly8vLCwsLMzIyzM3NFy9ezMvL29jYiNBZNt3d3QoKCgICAmhrY/5Dj42NXb58ubCwMP1oQhA7inZQgQrr4cOHQ0NDwDwVEBCgN85CQkLWrVu3bt06tL8TQZCqqqozZ86gV3T//n0mJiZDQ8OpqSlHR0dWVtbTp0+jvaf01UdpaamQkBAvL29NTU1lZaWAgAAEQdra2qitQ6VS7927x8TEZGJigna6TE1NEQiE2tpaDQ2NrKysiYmJCxcuMDIybtiwQVBQEIioo6MjBEGgfwVBkP7+fllZ2evXr5ubm1tbWxsbG/Px8TEzM/v5+aFXUV5erqCgAIaLgRDW1atXa2lptbW1jY6Onj9/fvHixSAiBobhvLy8VatWnThxgl6G0aglYFjPaejcvHnT29sbfE2dnZ26urp8fHz79u0TExPbu3cv8EDQx0z6+fmhxWtpadm/fz8EQXv27NmzZ4+Pjw+9BAICAgLExcURBGlsbOTm5oYg6LfffrO3t+/r6wPCtnz5cvQdA8LGwcEB3BgzMzMjIyNAnhsbG1++fAn8B1QqNTY2ds2aNezs7Hfu3NHQ0ACtIi8vL2ZmZkVFRfSTn56efvHixbZt20CfAhpI5ePjs2XLFhkZmatXr0pISKxatQp43VF1+fTp0549e2RkZNrb2318fFhYWPbt2wc8MSju7u5ycnJgHIuIiAg7O7uoqCjqngHBvcAWRxAEh8PdunVryZIlysrKwE0C3hl9fX1mZmZjY2PU5dvQ0GBoaAhaRerq6siCYGEKG5FITEhIkJCQ2LBhw+XLl0GP6PcS19fXy8nJbdiwQVxcXEFBQU1N7dixY66uriCabmpqysPDQ1FRsaWlhT6T0NBQPj4+tPb58uXLtWvX1q9ff/MVxCsAACAASURBVPLkSTCwCST79OmTgYEBNze3lJTUN80I0B0iKipqa2sbEBDg6+t79uxZJSUlMNhlYmLC1NQUVMQPHz4MCAgICAiQlZX18fGh0Whv377l4uLi5OQ0NDT08PA4deqUtLQ0aGN2d3efPXv21KlT6GiE3t7emzdvMjMz8/HxVVdXg4Z/c3PzhQsX1qxZIysrGxERUVpamp+ff//+fXBGHA43MTHh7e0tKSlJX62TyeSIiAhQ5UVGRhKJxImJiaCgoE2bNvHw8Lx584Y+aHtmZubDhw979uxxcHBAq6Hc3FxQaV6/fh3UKeXl5SCcwczMrLCwsLS01M/Pz8DAIDMzs6io6Pz585aWliBbKpWakpLCyMgIQdDjx49BsxeGYSKRmJ2dvWfPHg4OjvDwcLTDYM4Nz8zM3LFjx/Lly21sbCorKysqKrKysvT19W1tbUH7enx8/OLFi8BsIhKJdXV1wGXHy8ublJQEqrDa2lpQC1+5cqXyD1xcXJSUlECrYmpqCkSgaGhojI2NoSF2169fx+FwYJYW1M0IRkqsXLkSyGRUVNTKlStBLdPb20smk6enp4GxoqamVlVV1dHRUVhYGBoaWltbW1JScv78eTDerq6ujoeHBzTmJicnZ2ZmQPtDUVFxZmZmenr63bt3fHx89OMfQJ/x5cuXR0dHQehpbm7ujRs3QGDtgwcP2NnZFy1aBMbMdHZ2ysvLMzIyurq6gtfgyZMnrKysJ0+epI/EQX1rS5YsYWdnd3FxGR4enp6eHhoaamho2L9/PxoaEx8fr6mpiX4Xvb29a9euhSDI19cXfYW8vb2BxQaorKwE41MhCHJ3d59jsiMI8vLlyz179iAIQiQSHzx4wMDAsHjxYuB7+PLly+HDhxcvXox68D59+gRBEDs7+9evX2dmZohE4ufPnysrK2dnZ1taWoKCgtDWz9TUlJOTEwgJPnr0KBg5U19fLyMjw8HBAYYbomWIjIxkY2PbuXMn+IqJRKKZmZmzszPYOzQ0pKenx8jIePXqVTRkt66uTlRU9MSJE+Pj4729vaA5pa6uDl4nBEHAO4B+hp2dnRcvXgS3F2yhUqnp6elv3rxBm484HE5XVxd0Ijo6OoKNBQUF69evX7t2LX338ODgoIqKCgRBQP8WAAtT2AgEQnFx8du3b+Pj49++fdva2vrjsYcEAiE1NdXX1/fOnTs+Pj7V1dVoFYzD4eLj45OSkurr6+kzgWG4uLi4qKhoZmYGxEq5ubklJiYmJSVVV1ejn2VqampYWBiYrQMNuptDY2MjiF28efOmtbX1hw8fUB9Ff3+/kZGRtra2np7erVu39PX1dXV1PT09u7q6iERiVFSUlpbWjRs3dHV1DQ0N37x5g34nQUFBV65cuX37NohdRhCktLT01q1b4CwBAQHo29/d3f3q1StFRcWtW7fy8/OLiopeunTJxcWlvLycTCYXFxfr6OhISkqCfECd1dHRoaOjIyQkpKGhYW5u3tLSUlhYePz4cTk5uRs3bgQFBaHdeCDx6dOneXl5z58/j5ogzs7OW7Zs4eHhOX78ODBx4uLiNm/ezMvLy8fHx8/Pz8/Pv3XrVnt7+/T0dH19fQEBAX19fXD42NjYnTt3gIieOHECNUlra2tv3LghICCwadMmTU3N74V6UqnU8PDwvXv3btiwgZOTk4uLi4+PT09PDx3kFxcXt3v3bhBgArpS8vLyjh49umLFir17975//x5okoWFBRcX15o1a7j+4PDhwyD6H4bhoqIiFRUVECMDarenT5+uWbOGh4cHGIJoeQYHB+3t7Xl4eDg4OGxtbfF4PJVK9fT0XLVqFS8vr7Ozc3d3d0dHx6lTpzg4OMTExNTU1HR0dE6dOnX//v26urqXL1+eOHHCxcUFzK+mra3Nx8cHpKKgoEBaWhqEgJaWllZUVKioqJw+fRpt64yMjNy9e3flypXbt2/39/cfHx+vqKi4ffu2iopKTU0NDMM4HE5WVlZZWbm5uXl2djY5OVlUVBSYoZOTkzgcTlNTc8mSJVJSUp8+fZoT5tDZ2WlgYLBq1apVq1Zpa2s/e/bM2Nj48OHDZmZmvb29FAplZGREXV1dSkoKfdv7+vqOHDnCxMR0/vz5lpYWEokEzA47O7vp6WnUI1dZWbl3797Fixc/fvx4TtAggUDw8PAQEREB4l1XV7d582Z1dfXBwUECgfD27dvdu3eDaM/p6WkqlZqbm7to0SJ2dnYvL69Xr169fPny+vXrDg4O7e3tqampFhYWHz9+RL/liYkJfX19VlbWgwcPooOs09LSREVFt27d6uLiUlpa2tTU1NDQYG9vv2bNGjk5ua9fv+Lx+JiYmFOnToHYKwRBJicnwVCQrVu31tTUUCgUMAhy06ZNx48fLy0tJRKJ+fn5QOO1tLSGhobGxsY8PT2lpKTQ4SUUCsXGxgaCIH5+/traWhiG8Xh8UFCQp6dnW1sb2p6rqKg4duwYMzMzqlhEIhH0uO/fvz8pKamlpaW7uzs9Pf3IkSNr1qyZM5D/12VhChsMw2DORjCH4c+MqIdhmEwmEwiEOaEfIFAQTKU4/yj63iAikQhORz8pJYlEAo1fNOjom8zMzExOTk5MTExNTdHHr9NoNDwePz09TSAQJicnQRo06nJmZoZAIExPT+PxeFAhogeC9FNTU6gLfnZ2Fs2KQCDMmYNgYmICjOMZGBiYmJigPwqMnKMvPIVCGR8fHxsbIxAIeDyeQqGQSKTh4eHJyUkCgQDuA33ikZGR4eHhsbExtIR4PH54eHh0dHR0dBSE9gAv0Ojo6ODgIA6HAyWZnp6enZ0dHx8HmYPDaTTaxMQEOBYMZwZ5tre35+fnt7W1jYyMjI+P/2DqIAqFMjQ0lJubGxAQEB4eXlNTQ9/cLiwsDA4OjoiICA0NBWHcFAqlpqYmLCwsJCSksLAQVKZEIrG2tvb169cvXrwIDAwMDQ0tKSkBJ52dnf3w4UNkZGRERMSrV6/AuOnJycns7OzAwMDk5OTBwUHwhoAJI1JSUkJDQ0EDCIj30NBQcnJycHBwQkJCV1dXT09PQkJCWFhYREREZGRkVFRUSEhIQUFBc3NzbGxsREREUlISDoeDYbizszMnJwdE1iUkJDg6OkZFRb169So3N7epqSkyMjImJgY0WRAE+fDhg4WFxePHj/38/MLDw7u6uj5+/Hjnzp2AgIAnT54AYwgcC8Pw169fnZycVFRUVFRU7ty5k5iYmJ2draOjo6Kicu3atfkzlcAwPDo6GhUVJSsru2HDBmlp6WvXrr1+/RrI2MDAgK+v7/nz5/X09EBlTaFQ8vLydHV1L168ePXq1Xfv3rW0tDx58uTixYv37t2bE1JUUVGhr69fUFAwxyIvKCi4fPmytrY2mCUAmFng2KysLGNjY1VV1YsXL969e7ekpGRkZOTRo0eqqqpXrlzR1tbW0dHR1tZWVVWNiIiIj4/X0NCQk5NzdXWlHy7W3Nysr6+vp6eHBoLRaLTS0tL79++fOnVqy5YtW7duFRAQkJWVNTIyAnO/paSkyMnJCQkJeXl5gc+qtrb26NGjFy5cuHLlCmjl5OfnKygoSElJnT17Vk9Pr6Kigkaj+fn57dixQ0tLKykpKSwsTEREZMOGDaAHF0GQtrY2TU1NEN+koaExOztbWVkpLS0tLCwcFRWFfr8wDH/48EFWVhYY2QCg8RcvXhQQEBAWFlZUVNy7d++ePXtA4Mn3vppfi4UpbBj/XwH/MeX0NxsfPwDM+Iz+BKYYiUQikUhArUkkEiqQZDKZRCIRiUT6phI6tzXamgF7p6amwLzbMzMzwJYC6YG/C211wX/M2Q0yAVNgo5oHWktkOkA0DZjUG/ycmpoCW9CzgGxpNBpoBpHJZCKROD09DcoPEoNT4PH4kZERIpFIJBLxeDyJRCIQCMPDw+AvuJnT09Pgn5mZmeHh4cHBwZGRkcHBwfHx8ampqcHBQbBxeHj4m+02Mpk8ODgIpinp7+9Hg0vJZPLw8DAOhxsZGcHj8aDA4LwgQzwePzMzMzQ0hMPhhoaG0BEsKOPj42C6cPoWzNTUVG9v78jIyMTEBMhzamoKPCw8Ht/f3z80NATKTyAQQJMLAFp1oDlFIBAmJiZ6enq6u7uHh4fpW7owDI+Pj4+MjKDzj4Ptk5OTXV1doIf+8+fPXV1daNNqYmKio6Ojvb19bGwMPBoikdjR0TE8PDw0NDQwMEAmk6empjo6Ovr6+vr7+3t7e4G7aGZmpre3d3BwEDTjvn792traisfjwXmBOdve3t7W1tbV1UWj0aanp9vb279+/To+Po7OY44gCIVCGRwcBK5m9EKoVOrQ0FBzc3NpaWleXl51dXV3dzdosdEf++uCCRvGL8+/K47rm/nM3wjTTXI4P/E3d30zk+8V+29fC/2B//oNoS/e38vte1f39676m4X5QWz6v17+Py3Pn75433zoP5n5j8/7pyf6QZ4/zhwL98fAwMDA+BF/SST+Xe2zfz2TXx1M2DAwMDAwFhSYsGH8w6CuFXge30w5x8X0p/xpJj9IgDV+MTB+RTBhw/hf5Meigu6aEzuAbvxBJn+pXwQTNgyMXxFM2DD+YSYmJlpaWnp6enp7e0GI1/fkBAxVpo/aAv9MTU319fUNDg6CGEJ0yzcz+Rk7DI/Hg1lXMDAwfkUwYcP4h2lra7OxsdHQ0NDS0jI2NtbT07OysoqOjqYfWwakqKWlxczMLC0tbY6VlpKSoqure+PGDU9PTzDJVmdnp5WVlZ+fX2BgYFhYGDp9A6C5udnT0/Pdu3fzC/PlyxdfX18jIyMdHR0wKd/81cDz8/NDQ0O/J5wIgnR0dIA5Yvz8/NLS0np7e7Ozs589exYeHk4/K+PMzExISIiPj8+LFy8GBgY6OztDQkLAUR4eHq6uru7u7k+fPs3Pz6efzg3Q3t7+/PlzFxcXFxeXR48effjwAZ3bbGRkJDw83M/PLzMzk37JmMHBQV9fX39//9evX+Px+MTERG9v78DAQB8fHzc3NxcXFy8vL3RuexiGq6urnzx54uLi4urqGh0dDSaS7+3tTUpKSklJyc7Ozs7O7uvro28lTE5O1tXVoatcfu/+YGD8p8GEDeMfZnh4GCz/wcrKam9vf+/evQ0bNrCxsaErXAMbCyySAtYiQeeFAbVncnIymM/3yJEjYJWpwcFBIyMjMPGSmpoa/Zx7NBrNx8cHgqBTp07NmbO/r69PVVVVQEDgypUr+vr6QkJCx48fR+eYABCJRLDeZkREBPKt6huG4fLy8p07d4KzW1paNjY2enp6Ll26FIKgGzduoLNP4fF4HR2dFStWnDp16uvXr9XV1VJSUmCyeTExMSkpqX379vHy8u7cudPGxubLly/AVJ2dnc3Pz1dVVd2+fbuEhISkpOTOnTu3bdtmamoKcu7q6rp06RIDA4OAgEB0dDRawra2NjBL/c2bN4eGhh4+fAgWfFiyZMmBAwckJSW3b99++PDhyspKIpEYExOjpKS0f/9+SUnJo0eP7tq1y9PTE4/HNzY23rp1S1BQcM+ePQYGBvSzxyEIEhsbKysrGxgYiPVQYvyzYMKG8c+Tl5cHllUEP9EFrFHrAUGQhoYGWVlZBgYGLi4udJF7dMzNnTt3wBoraJ7d3d0MDAzMzMxg5gi0kh0bG7ty5QpYFWHOJGc+Pj6srKz+/v7gZ3V19aNHj9DFuAH19fVgriNDQ0Mwwcd8qFRqSEjIqlWrdu7cCTS1p6cHzD+5ePFiKysrdMwvhUI5e/YsOq1GfHw8BwfHwYMHwdTP4+PjaWlpJ06cgCDo3LlzQLeysrL4+fk3b96MzvXX1NSkqKgIlqcBM6V9+vQJTBa8a9eu1NRUdNz658+f+fn5UVsTzCSpo6MDZmL78uWLp6dnQ0NDR0fH9u3bd+7cidqX9+/fv3fvHjB86+rqxMTE1qxZg075CCCRSGBhbkVFxQ66lfYwMP77YMKG8Q9DoVDi4uIgCNq4cWNNTU19fb20tPThw4fRufYBUVFRW7duPXToEBsb28OHD+cYW2A+/rt374Kf09PTNTU1QNjAakGoAZGbm6uoqLhp0yZWVlYzMzM0fxiGgTra2NgMDQ2BxGNjY2BhFPiPCYudnJx2797NysrKx8f3vbXCaTRaYmIiFxfX8ePHm5qaEARpb29XU1Pj5ORcsWLF2rVrX758CTycU1NTQkJCYEF2BEFiYmKAsNGbmC0tLZs3b4YgKDs7m0wmg2lt0Rl1AZWVlWB29tTUVBiGq6qqJCQkVq9eDRYuQWcZrqmp2bJlCzoJ8uXLl8HapOiDAC2JkpISZmZmCQkJdKElMC0q0OP29nYlJaWNGzfSz6KLIEhSUtKuXbtYWFjWrl0bEhLygyeOgfGfBhM2jH+YiYkJBwcH4Io8efKklJTUihUrEhIS6KcyGhwcdHBwMDMzi4mJWbJkybFjx+bMcayvrw/WMu7t7a2urg4ODra1tQV+NvqFy6enp+/fv+/l5fX+/XtmZuZTp06hZ4Fh2MnJiY2NjYOD4/LlyxEREc3NzajJCHr1cDicjIxMRkbGmTNnGBgYHBwcvjkNKQzDCQkJ69atu337NrDqmpqaTExM7O3tXVxc2NjY1q5dGx4ejiDIzMyMoKAgWFkNQZDo6GgODg5xcXHgUAUQCAQNDQ0mJiYfH5+WlhYJCYmVK1eCBSSRPxR3ZGTkzJkzYLFsEolUWVl548aNBw8egEniz58/D4yt2tpaQUFBVNhkZGQgCLpz505jY+OnT58iIyNBv2NSUhILCwtwnEZFRX3+/Jl+TbXGxkYpKSlubu45wnbu3LlLly5dunQJLLc7Zyl2DIz/JpiwYfzDwDCckpICQdCaNWtCQ0MjIiJkZWUPHjyYnJyMGmSRkZGysrIFBQVVVVV8fHzLly9PTk6mDyEBwrZr1y5jY2MDAwNtbW3QE8bGxka/cHliYuKFCxcSEhJKSkr4+Ph4eXnR5dMQBBkYGLh8+fKKFSvY2NjY2Ng2bNhgaGiIrqJHIpHCw8NVVVVbW1tDQkJWrFghJSUFYlXmX1FCQgIXF5eCggKYAbmpqcnQ0DAgIGB6etrS0pKBgWHPnj2fP38mEonCwsJ/Kmw6OjrMzMwPHjzIzs4WFxdfu3btHGED68axsrJ6enoCYdPU1ExPT8/OzhYUFGRiYrp06dLU1FRnZ+eFCxfQTj4gbBwcHHx8fFu2bDlw4EBcXByCIDgc7sqVK8uXL1+2bNnSpUvXrVunq6tbV1cHXJqtra1KSkpzhG1gYODEiRNxcXE5OTm8vLwiIiLfW8sCA+O/ACZsGP88GRkZYFFKsIzA8+fPOTg4DAwMwPI3MAxbW1uvXr0arPHIzc3NyMh45coV+i4u4IrU0tIaGBgYGBgYHBzMz88Ha3GhwgbDsKur644dOy5fvnz9+nUBAQEWFhZ0TWqgEOPj4yUlJY6OjrKysmvWrGFhYUHXRx4cHJSXlz9y5MiLFy+8vLy4ubkXLVoUFBSEzBtCAMNwfHw8FxeXqqoqCCZsamoCKyIhCNLa2qqsrAwWwCwoKBAREUFdkd8UtunpaQ0NjUWLFvn6+paWlu7fv3/16tWJiYn05x0eHj579iwLCwuw2CoqKrS1td+/f0+lUpOTk7ds2QI0r6WlxdDQEDV2gbDdvXsXhK44ODi4u7uDXWNjY6mpqY6OjhISEkuWLFm8ePHJkyfBUn/l5eUiIiI8PDz0S/RFRkaePXsWrD8gICDAwMCAZoWB8d8HEzaMf56PHz9CELRlyxYwCu39+/fr1q2TlJQE1lJJScnly5evXr0aGBgYGBj44MGDtWvXrl69mt4UMzAwoO9jQxCkq6uLvo8NQZDm5uYzZ84oKSm9fPkyODj43r17ixYtEhERAas/02i0pqYm4Jmcnp4eGBhwcXGhX346IyNj165dt27dunXrlpqamqioKARB+vr689dnRy02Y2Nj4MRrbm42NDR8+vQpSFBeXr59+3YGBgZJSUkODg50nWVU2NAl0xAEGRsbO3DgwPLly0tKSohEopycHCMjI/3amwiC9PT0bNu2jZGREfSxFRUVPXv2DGRCpVK9vLwYGRk5OTnPnTt38+ZNdP0zIGzPnz8HP/F4/MDAAP2FEAiEvr6+zMxMYWHhVatWJScng8chICBAL2xUKlVCQoKfn19TU1NcXBy4MU+fPg3i/jEw/vtgwobxzwOEbdOmTaDLytbWds2aNW5ubmD8lpubm5aWFg6HAyvMdXR0yMjIMDIyenl5oQsog+WqPTw80DxbW1shCGJiYgLOQARBYmNjr1+//u7dO7AoXXV19W+//cbGxubt7Y0gCAzDxsbGYAE2wMuXLzk5OR8/fowgyODgoLGxsYeHR1tbW0tLy+fPn1++fMnDw7N7925gx8whMTFx3bp1Ojo6oHIHwoYuNQnDcGxsLIi2hyAI9dpFR0evXLlSXFwc9XCSSCTQLWdrawviTVxcXBgZGc+fP0+/aPX79+/Z2Njk5eXBxqKiIgcHh5KSErB3aGjIxMSEgYFh0aJFmpqa6ADBOcKGIMjo6GhNTU1cXBxwaaLb5eXlBQUFy8rKEAQpKyvbvn07Nzc36sUtLCxUVFR89epVY2NjaWnpy5cvd+3atXr1anShagyM/zKYsGH8w+DxeEdHR1DFHzp06OjRo9LS0k+fPh0eHqbRaKGhoatXr963bx/a15Wbm8vPzw+EEDjx3r59C+IGz549C2RsdHTUzs4O5GlnZzcxMZGZmSkqKiouLg5qZwRBysvLQT/chg0bMjIySCTSsWPHTpw4YWNj4+TkZGFhsXv3bllZWRwONzU15e7uzsXF5ePjgxo0ycnJGzduhCDo2rVrc6Yp6evru3fvHgMDw7Zt20Ao4/v372VlZS0sLFC1IJPJ4eHhq1atgiAIXRY5ICCAiYlp1apVenp6zs7OFhYWCgoKR44c8fHxQf2uOBxOVVWViYlJRUUlNTU1KyvL2dn5yJEjZ86cqampASvTvnz5UklJCUSCgJ7I/v5+0A2poqIChA2Pxx88eBCCILAKpaOj4927d01NTZOSkpydnUVFRcPCwkpLS0tLS/38/ERFRV1cXMCqtuCJrFy5MiYmBkGQoaGh69evo2EyYAvwtcrKyvb39/9HXhoMjB+CCRvGP8zMzExpaWlYWFhoaOjjx48fPXqUnp4OBIBCoZSUlAQEBMTHx3d3d4PoxNbW1piYmLCwsLCwsOLi4pmZmbq6uvDwcLACNZiAo6enx93dPTg4+NWrV9nZ2TMzM6mpqY8ePUpISED9Y/X19WZmZnfv3gXzg0xNTcXHxxsZGRkbG1tYWFhaWv7+++/l5eUIggwODjo6Ouro6ERHR6NzeSQlJbm5uYGU9CEkMAw3Nze7urrq6Ojo6+tnZ2ePjo4mJyebmJgEBQWhbkAEQWg0WlhY2O3bt1HNTktL09bW1tPTMzU1BTm7u7unpaWhsZdAVr9+/WpnZ6erq+vn5/f8+XMbG5uHDx+i3suBgYHQ0FBzc/OMjAx0TVEEQTo6Ojw9PYODg4HlNzAw4OTkpK2tfffuXSsrK0tLyzt37jg5OX358qW2ttbQ0PD8+fMaGhrGxsZmZmbBwcHgvvX394eFhRkaGmpqajo7O3d2dr5+/drU1PTJkyfo4ss1NTVqamp8fHzHjh0D3ksMjP8ymLBh/I8yf+qK+VvAitLzDyQQCPSeOgRB6APWATMzM+3t7UBpxsbGQHj68PBwe3t7R0cH/eHT09NtbW04HA4YkeAUOBxuenqaSCT29PSA9ZpBYrB0dXd3d19fX09Pz+joKChMW1vbwMAAkUiccwnDw8OoWI6Pj4MDu7q6wJLT37snNBqts7Pz69evzc3NXV1d6LxfYEhDd3c3ON2c0X4IgkxOToIZTAgEwuDgIChkZ2dnV1dXZ2dnf38/ENGurq53797FxcV9+PABlW0Yhqemprq7u3E4XGtra2lp6cDAQFVVVWtra3t7O+oW7uvry83NTUtLy8zMBFOTYCO1Mf7LYMKG8Q8Df58fp/nB3vm70J9/o2zf3P6nW36Q51865JtX9DMp6TfObyL8ZGl/5rz/oQMxMP42mLBhYGBgYCwoMGHDwMDAwFhQYMKGgYGBgbGgwIQNAwMDA2NBgQkbBgYGBsaCAhM2DAwMDIwFBSZsGBgYGBgLCkzYMDAwMDAWFJiwYWBgYGAsKDBhw8DAwMBYUGDChoGBgYGxoMCEDQMDAwNjQYEJGwYGBgbGggITNgwMDAyMBQUmbBgYGBgYCwpM2DAwMDAwFhSYsGFgYGBgLCgwYcPAwMDAWFBgwoaBgYGBsaDAhA0DA+Ofh0ajkclkGIb/6YJg/GKg7wz9y4MJGwYGxj/P1NRUQ0MDmUz+pwuC8YsBwzCNRoNhGBM2DAyM/y0oFMrk5CSNRvunC4Lx69He3t7b20u/BRM2jF8e0GRD///TxHMadz954M8U45s5/72s/tL2/zT/ynn/XfcE438BIpHY19c3NjaGbvmZL+5fOeP09HR/f//k5OQP0hQXF+fm5hKJRARBOjo60tLSMGHD+OUBVefo6Oj4+PjPpAcqSCAQwsPD7ezsnJ2dU1NTKRTK3zj1zMxMW1tbcnJyTk4OWpi/kc83GRsby8jIcHd39/f3z8vLA992f39/VVVVa2sriUT6d50IhUAgNDQ01NfXj4+P01/I37uosbGxtrY2TNUWErOzs5OTk0QiEX2sVCr169evU1NTc1KOj483NTWNjY39iy9AY2NjVlbWyMjI9xLAMDw8PIzD4YAfu7+/v6ysDBM2jAVCZGSkjY1NX1/fj5OBz6yuru7Bgwf+/v7x8fHe3t4aGhppaWkzMzMIneH1TZD/a4IQicTU1FQJCYmrV6/S5/+n+dDnRl828BOHw7m4uDg5Ofn5+VlaWj548OD+/fvnz5+vqqoaGRkxNDQ0MTHppWKZ7QAAIABJREFU6ur68Vn+9I7NTzk2Nubu7q6oqJiVlQUSODs7JyUl/b2uLwKBMDg4iFlsCxsajTYwMAC+HXrGxsZqamp6e3v/RXN/YGCgo6Njdnb2B2nmlIdMJmPChrEQgGFYTU2Nh4enpqbmT1OSSKQnT54oKSn19/cjCDI9PR0fHx8bG0vv7phTHcMwTKPRgKkHeqrRjRUVFdLS0hcuXEBTortgum5tGh308oPmhh7b1dXl5OR08+bNN2/efPnypbOzs7W1NSMjQ1BQMCEhAUEQExOTc+fO1dXVgcLMP8X8wn9T8+YLG4lE8vf3Z2ZmDg8PBwnu3LkTHBw8v9r6S2DC9v8hFAoFj8cTCIR/JZO//eZgwoaxEPj48aOent6JEyccHBz+NPHAwICJicn9+/fnbBwZGZmYmAA/iUQihUIZGRnp7++nby3O/9J6enru379vb2//vdP9pY9zbGzM1tZWQUGhpaVlzq6PHz+2t7cjCBIcHGxgYECfgF4d/0UqKir27NkTHR0NMiQQCJOTk1Qq9d+SOQbGfwdM2DB+eWZnZ42MjF68eBESEnLixInOzs4fp+/q6lJTUzt06FBeXt7o6CjqZ+vv7/fw8PDy8iosLJyeniYSiQEBAZaWlrW1tbGxsSEhIV+/fqVSqSMjI3FxcbGxsQMDAwiCdHZ2GhoampubIwgyMTHx6tWr8vJyEon0/v37gICAzs5OGIY7OjoiIiKSk5MnJyenpqZSUlKCgoJycnLS0tL8/Py6u7vRshUUFBw5csTY2Bj8ROWKPlwwMDBQV1c3IiIiMDDQx8fn06dPYDuBQMjJyUlISPD29k5OTsbj8QiC9PT0xMbGRkVFpaSkJCcnBwUFJScngz6SoqKihISE169ff/jwYXBwEGRSVlZ28ODBuLi4mZmZzMzMqKiolpYWLFgR49cCEzaMX56amhpHR8eqqqqhoSFTU1Nvb+8fpwc9SevWrdu6dev169dtbGzev38/MDAwOTlpbGwMQRAwv6hUqpWVlaysbHl5uY6OzsaNG4OCgshkcmdnp5qa2q5duz5+/IggSG9vr4qKyuXLlycnJ93c3OTk5GJiYggEgouLCwRBERERCIJUVFSIiIhs3ry5oaFhZGTEwsJixYoV+/btU1FR2bFjR3FxMVq20NBQYWHhJ0+egJ/f7KAKCQlRUFDQ19e/dOnSrl27Ll26NDAwQKVSGxoaLCwsLC0tlZSUdu3aFR8fjyBIZmbmxYsXDQ0NXV1dL168CEGQqanpxMQEDofz8PCwsLAwMTGRlpb29fUFmWdmZq5cuTI2NnZmZsbb21tQUNDNzQ1oJAbGrwImbBi/PA4ODkZGRkVFRZWVlaqqqlJSUtPT099LDHRieno6LCxMVlb2wIEDQkJCPDw8FhYW4+PjY2NjBw8efPDgAQzDY2NjERERUVFRCIL09vZqaWmFh4eD3qbi4mJNTc33798jCILD4VRUVMTFxd3c3M6cOdPc3Iyea//+/cHBweB/V1fXAwcOVFVVIQjS39+vpKQkKir65s2b0tJS1P+JIMizZ8+4ubmfPn2KlpZGo01OTo6MjExOToKzh4SESEtLx8TEgJIcOHAgMTGRRCK1tLS0t7eTSCQ8Hn/w4EENDQ0SidTV1dXY2IggSHd3971799TU1IBKtbW1jY6OIghCIpGUlZUVFRVBd0hBQYGAgMDr169BAczNzZ2cnEBnJAbGrwImbBi/NsPDwzIyMgcPHjQxMTE2Nj558qSgoODbt2+/l36+AdTe3n779u2NGzdWV1cjCPLgwYPr16/39/dnZGRYWVn19PQgCNLZ2amjoxMeHg6C7IuKiq5fv44Km7a2NgRBnJycQUFB9Dnv27cPFbY3b97cuHGjvLwc5Hbx4kV9ff354xMSExP379/v6uqKbpmdnS0pKQkODnZ3d8/NzUUQJCgo6NatWw0NDQiC1NTUXL16NSkpCVxXR0fHhw8f3r59Ky4urqysjHplOzs7dXV1T506BWIpEQQhEolfv379+PFjamqqjIzMgQMHgEuzsrLy+PHjMTExIEMzMzMnJyfgdMXA+FXAhA3j1yYmJgaYa319fV1dXQ0NDRcuXFBXVwd7YRimUqkUCoV+BPfs7CwYy4lSV1e3ffv2kpIS8L+ysvKzZ8+Cg4PRkJCWlpYrV668fv0ahFHk5ORcu3YtLS0NQZCBgQENDY1ly5adOnXqxo0bQB0BYmJiILwQQZCIiAh1dfXKykoEQdrb27W0tGJiYuaH0ZeVlR06dEhVVRUdV0elUoGvddWqVW5ubgiChISEGBgYfP78GUGQqqoqMFaBQqFUVlaqq6sbGxu/e/dOU1Pzxo0bra2tCIKQSCRbW1tRUdH09HSQJ41GS01NPXXqlIaGRnJysra2tqysLAizzMvLW79+fXR0NEh5//59FxcXtAcOA+OXABM2jF8VGo02PT2trq6OigfAw8Nj8+bN9fX1CIJQKJSioqL09HT6uRKampqio6NramqAShEIhPT0dCsrK2DfwDB8/fr1xYsXW1lZdXR0gEM+ffq0c+dOb29vEMHs5eUlKSmZmpqKIEh3d7eCgoKMjMyXL1+UlJQOHz5cVlYGDLvdu3c/e/ZsdnZ2enpaR0dHWFi4oqICQZAvX75cvnw5NDR0/iBrKpXq6uq6c+fOiIgI+mjMhISEZcuWgSv18fHR0tICBlZVVdXly5dTUlL6+/slJSVv3brV2to6PDx86dIlZWXl9vZ2IpEYFRUlIyOTkJBAIpGmpqaKiorGx8e1tLQMDAyamprAwDgFBQUwBPDjx48cHBygaxBBEGNjYwcHB8xiw/i1wIQN41dlaGjo+fPn69ev9/HxQTeOj49bWVktWbJEWVmZSqVSqVQLCwtVVVVg3wA6OzvNzc2vXbuWk5PT1tYWERGhpqaWn5+PBrW7ubmtXr360aNHyB+uy7a2toMHD4qJiYWFhfn4+Jw9e5aHh+f58+cUCiUrK0tMTOzw4cODg4OfPn2Sk5M7evRobm4uDMPHjx8XExMLCQnx8/M7cODAzp074+LiYBiOi4sTEhLS1tYGvVxz6OzsvHbt2o4dO6Kionp6ekgk0szMjKen58qVK9+9ezc7O6ujo7Nv3z7gCK2rq1NUVLS2tu7p6ZGXl1dSUnr9+rWFhcWqVavk5OTq6+tfvXrFxcUlJSX17t27jIyM0NBQBQWF5ubmCxcuKCkpxcfHOzs7c3FxnT59emhoCIZhPz+/1atXP336lEwm43C4K1eu3L59+08DTTEw/qfAhA3j1wOIDYlEyszMzM7OBtNbgF19fX15eXllZWV5eXlAqDo6OpqamtBwEhiGgdfu4cOHhoaGxsbGUVFRjY2N9MZTbm6uj48P6MQCzMzM5OTkeHl5hYSE5OfnNzc3v3r1KjY2tqurq7Cw0MvLy8/PD2jn58+ffXx8wJSsmZmZampqenp6ubm5FRUVgYGB79+/7+npSU9P9/T0DAgIaG9v/+YQse7u7qioqAcPHty+fdvQ0PDu3bv29vbx8fGTk5M9PT3BwcFubm7/j733jovqyv//zScPs9kkq0mssUUsidh7QVBALChIEQHpTTpSBekgTYo0ARWQDiJdusDQmyO9M/QOw8AwDNPL+f1xfnuXVWHVZPebmPv8C+7ccu65957Xeb/P+7wPBoNhMBgEAiE+Pj4mJmZgYCAzM1NJSUlbWzs5OTk9PT00NPT169clJSWOjo4hISEvXrxISEiIjo5OSEiYm5tLSUlRUlJSU1PLysoqLS0NDw9vbm6emZmJiory8vJKSkrq6el59OiRl5dXWFgYKmwofy5QYUP584Ek7Hg3IwaNRkM8eO+NlYdbOBwOHo9va2tramp612zy8/N79uzZ4mE5eNT8/Pz09DQ8P5PJnJ2dXVhYIJPJRCJxfn4eSZdHoVCQPCBDQ0NdXV1QNeGeFAqFRCLNzc3Bv5eaW81mswcGBurr6+vq6urr64eGhpB4ThKJRCQSSSQSHDtcWFggEolUKpVGo/X09HR0dMARxLm5ubm5OSqVOj8/Pzc3h8fjp6amCAQCg8HgcrkUCqWnp6elpQXWIdyZTqdPT0+TSKTZ2dn5+fmenp6pqanZ2dnfmHkEBeV/DCpsKH8+3puJ6q0dwL+nknrr2Hf3R/ahUCj37t2LiYlZfOa3LrFUmg/kPO+9ylKHfODGDy8GCspfHFTYUFD+hb29vaCgYGBg4NjY2HsNPhQUlD8+qLChoPz/cLlcOzs7AwMDOMn6d0zAiIKC8r8EFTaUt1nsT/vwQ/6bJfofweVykXGyj60BFBSUPw6osKH8i09rx9HWHwUF5Q8FKmwo/wLGGXZ0dLx58waPx/f09JSXlzc1NbW0tODx+KWO4nA4PT09tbW1Q0NDH7gONZfLJRKJjY2N7e3tbyUB+Y1QqdTBwUE0UwYKyl8ZVNhQ/o35+fn4+Hg5OTkrKysnJyctLS0HBwctLa1nz55BN927IRUcDicuLu7atWt+fn7vJj9cis7OTm1tbV1d3Z6ensXbP9lqZDAY9fX1sbGxkZGR0dHRaWlpnZ2dHyi0vx0ulzs9PV1dXV1UVFRaWookOllYWGhtbcVgMA0NDSQSaamAFC6XOzc319vbC2dJ/75GMJy6h8fjh4aG2Gz2bzw5LN7Y2FhhYSEOh4Pz8N4qM5lM7u7ubm1tHRkZeW/MKpfLbWtry87OfvPmzfz8PGr0o/y+oMKG8i9g+zIzM6Onp/ePf/zD29u7qKgIg8E4Ojq6u7v39fWBJYSnq6tLTk7Oxsbmw9PAz8zM2NjYyMnJwYT3CwsLTU1Nk5OTn7z0V15enoyMjJWVVUVFRVxcnKSkpIKCwuJMWv8RKpXa2dlJIBA+rQD19fW3bt1asWLF6dOnkcndY2NjdnZ227ZtU1VVhZkbl2rE6+vrzczMkCSNvy8LCwuxsbFWVlYwhf/CwsLQ0NBvWd24uLj45MmTYmJir1+/fndORUFBgYiIiLKycn5+/lJnePjw4aZNm/j5+WGaMRSU3xFU2FD+BZLRw9fX96effkLWaJ6fn29ubh4fH0d2gwtMLz7WysrK0dER2QdOT17+crGxsZqamrBdq6mp2bp1a3Z29uIdPnzhZiaTefPmTUVFReTqvb299vb2781ZtRSNjY0iIiKZmZkffggCnLhWWVm5Zs2aJ0+eIHlMuFxuXV2dhobGkydPljkWADA1NRUWFraMEvwWmExmTk6Oq6srdPxisVhdXV2YkfljQWa45+XlffPNN0pKSrCSEWGjUqlWVlYrVqywtLR87zsA64rFYvn7+4uIiNTW1n76jaGgvA9U2FDehkaj+fv7b968GYl6X1hYoNFoTCaTxWJNT08XFxeHh4enpqYutoesra2dnJygxdbe3l5aWkogECgUysTEBIFAgKHzs7OzU1NTZDIZtnfx8fGampp1dXVsNjszM3PLli0tLS1zc3NsNptGoxEIhOzs7IqKCmhYQKXE4/EtLS1tbW1waU3k6j09PSdOnECEDUKn09lsNofDIRKJk5OT4+PjBAIB6jHU5unpaZiPg06nc7nc3NxcSUnJ1NRUuHw2zCcyPz8/MTExMzMDvZ2Tk5PDw8MTExOLMxSDfzbrdXV1GzdujIqKWqz6ra2tenp6kZGRcGW1ubk5CoUyOzs7OjpKIBCQzgSsHCqVymAwZmdniUTi3Nwc1IC5ubnp6WlkKQCYWGtqagpehUajzc/PU6lUKpVKIpHgbiQSaWxsbGpqikajsdns+fl5PB4/PT3N5XLZbHZqaqqMjEx5eTnMQsJms+HSo4vrBwAAH9/ExMTCwsLiuerw766uri+++OKrr74qKytbXAnJyck7duzYsGGDj48PUgkLCwsEAmF2dhaeH74ALi4uhw8fhqsKwMvNzs7CuwYAsFgsGo0Gy0+j0WZmZhATEykMiUSanp5evA4qOvsQBaDChvIudDo9ICBg7dq1jx496u3tLSwsvHPnTmVlJZFIbG1t9fHx4efnV1VVPXfunJiYGKJt1tbWLi4uBAJhYGAArpnS39+flJS0a9euU6dOwVSN9+/f37Ztm62tLTwqLi5OU1MTqpS6uvo333xz/fr1Bw8ezM7ORkVFycvLi4mJHT161NLSEoautLS0aGlpGRgYqKqqioiIIKn3AQA9PT1CQkL79u1LSEhobm4mk8mIDIyNjRkaGoqJiQkLC1+8eBEahRMTE97e3vLy8qqqqhcvXkxOTqbRaMHBwZs2bTp//nxGRkZ5ebmpqamSkpKuri4vL6+8vPz8/PzLly8vXbq0a9cuXl7eFy9evGuOYLHYDRs2RERELF6Pprm5WUdHJz4+fmpqysrKSkZGxsnJ6e7du7y8vJcvX66treVyuU1NTQ4ODtra2rW1tV1dXebm5lJSUsbGxgAAGo129+5dMTGxjo4OLpfb2NhobW29f/9+QUHBgoICDoeTk5Ojo6NjY2Pj5+dnZGRUXV3d19dnb2/Px8cnIiISGRk5ODj47NkzZWVlBwcHqPRmZmY7d+50dXWtra0lkUhNTU0WFhbnz5+/evVqSkoKHIejUCj+/v4XLlwQERHx9vaGuf8X09PTs3379vXr1xsaGiLp/5lMppmZ2bVr16ysrO7fvw8A4HK5U1NTbm5uurq6WlpaL168QHQoMDBQVVWVSCRyOJzx8fGAgAAtLa3bt29D9+bg4GB8fLy3t3dmZmZCQoKCgsK9e/eamprgsRwOp6Ghwc7OTlNT097eHovFkslk2EFBhQ0FFTaUt6HT6UFBQatXr75+/bqRkZGEhISAgAAGg2Eymf39/WVlZdnZ2YODg8+fP1+zZk1ycjJs362trV1dXWHK3YcPHw4MDDAYjMHBQSUlpU2bNkFv1cDAwPbt25WVlaenp8E/ha2xsZHJZD5+/HjTpk1ZWVkjIyMMBsPLyysjIwOHwzk5OfHx8cGk+BEREdra2gMDA+3t7a6urojbEwDAYDACAgJ+/PHH9evX//zzz/v379fQ0CguLmYymc3NzU+fPq2qqmprazt//vy1a9dIJFJGRsaZM2fi4+M7Ojqio6OfPHkyMzMTExNz/Pjx0NBQuFx1SEjIhg0bRERE7t27Z29vPzw8bGVlVVpaWl9ff/fuXRkZmaqqqreqbhlhi4mJYTKZnp6e27Zt4+Pjy83NraiokJGRERUV7ejoWFhYSEpKOn/+fFBQEFxo5pdfftHX14eP48GDBx4eHtPT01VVVRcvXnRzc2toaHBwcFBQUBgaGsJgMAcOHFizZo2mpqaRkVFeXp6SkpKzs3Nra+vTp0+tra1hSkwhIaG9e/fCHoa9vf3Ro0cdHR1bW1sHBgZCQkLCwsLa2toMDQ0PHDhQWVk5Pz/v6+trYGCAwWAaGxvd3NzKy8vfutnBwUFVVVV7e/udO3fCpQYAAC9fvvTz8wsKCjp79qympiYAgEAguLq6WlhYNDQ0BAcH//LLL8jiq+Hh4Tdv3sThcGNjY05OTlZWVr6+vrKysuLi4p2dnZOTk87Ozjw8PGfPng0ICPDx8bl06dL58+fhc29oaBATEwsLC+vo6LCwsNixYwcfH19aWtrv+CGg/HlBhQ3lbaDFtnHjxpycnNbW1vr6+ocPH8JFOOHQCA6Hi4uLU1VV/f777589ewaPUlBQ2LJly7Fjx54+fUoikeBGGo3m5OS0c+dOJCLj8uXL+vr60AKLi4vT0tKCIz0lJSW//vorElQ5NTU1NDTU3Nzs5uZ29uzZ0NBQAEBwcDAPD09kZOTQ0BDizwT/dEwRicTy8vKgoCBra2tlZeVvv/326NGjMK8/HBEcHBw8d+7ctm3b6uvrMRgMHx+fo6NjY2Mj9NGxWKy8vDwFBQV4pwCAjIwMCQmJpKQk6Amk0Wgwyf3MzExAQMD69evfHTZ7r7A1NTVpa2vDiiorKztz5oyqqipMK1xeXv7zzz/D9T+bmppUVFTgOcfGxtTU1CQlJQEAZDL59u3bTU1NXC7XyMjohx9+cHFx6enpcXBw2L9/f3Jycm9v74ULF44ePVpbWzs8PEwkEk+cOHHjxo2xsTEqlTo6OgrzIBsaGvLw8MBHk5ycLCcnV1hYSKfT4T7Qy/fixYvVq1fn5uYSCAQVFZUbN27AcVYCgUAkEt8KEnnz5o2FhUVbW5uIiIi+vj6cYmFqahoZGVlSUnLkyBE7OzsAAIPBwOFwcLkDKpX666+/qqurwwcdFhZ2/fp1LBZLo9G6u7vHxsYWFhbKy8t5eHjy8vLYbHZJSYmgoKCRkdHExMTc3FxoaOgPP/xQUFBAoVC8vb1FRETgonQlJSUiIiKmpqbvmpUof01QYUN5Gzqd7ufnt2XLFqSZmJmZmZubg8nmg4ODb968GRwc/PjxY3Fx8efPn8NREzU1tXXr1n311Vf6+vrQIAMAkMlkGxubnTt3IkEc4uLid+7ceVfYSktL9+zZgyhiUlKSvLy8h4eHh4cH7JgDANrb27W1tYWFhXl5edXV1ZHYlsWuJzgiODEx4erq+u2338bHx5PJ5ICAgFu3bpmbmwsLC0tKSra2ts7Oznp7e58+fXr79u0wfoHL5RYXF6upqSGmiaen55kzZ5D4Rg6HU1JSYmJicvv2bRMTk9WrVwcEBLxVdVDYoqKiFgtbS0vL7du3nz59CgCora2Vl5dHQh9HRkZ27twJvaPNzc26urqRkZHwWomJicePH4cJ+PX09EZGRgAAly5d+u67765fv25jY+Pu7u7n54fD4fr7+8XFxZWUlJAhKF9f38OHD+/Zswcuz0aj0SgUirW19e7du2EN5+XlqaqqNjY2wv3xeLyvr6+hoaG8vPzevXvz8/PpdHpCQoKgoODevXsvX74MrViwaASLyWSmp6cbGxtPT097enpu3769sLCwrKzs7t27ra2tJSUl/Pz8Xl5e8PwLCwsJCQmGhoZ2dnYbN25UV1eHKgjH2JAYloiICGNjY1NT0x9//BEG0cA5IYiFV1RUtG7dOjgI6ubmduTIETi89/z5c0NDw8Vrl6P8xUGFDeVtWCxWcHDwli1bhoaGwCLZePnypba2tqqqqpubG4yTvHz5MjLUdOXKFTk5udjYWDk5OXFxcRjrSCaT7927t2vXLugBo9Ppp0+f1tPTg61kYmKinp4ebI/Kysq2bt0K26nm5mYpKSk3N7eOjg4sFquvrw8tNgqFMjU1VVBQ4Onpee7cuZiYGGRy99TUVHd39+JZdFgs9qeffkpOTvb09JSSkgoKCqqtrXV1dTUzM+vt7aXRaC0tLXl5eSEhIbdv35aSkhoZGSkvL1dVVUWE7enTp1evXkWa3aqqKn5+fldX14KCgoyMjO3bt/v7+79VdbW1tatWrQoKClo8/Pbq1Stzc/Pi4mIAQEVFhbq6eklJCazYnJycTZs2FRQUgH8XNgBAV1eXhoaGubm5vr5+VVUVtPDExMT27dsXHh5eU1PT398PlQyPxzs7O2tra8P+BBweKykpcXFxuXLlyoULFzIyMhgMhqWl5Y4dO6CwZWdnq6ioYLFYAEBDQ4OOjo6enl5aWhrstWRnZ8OpbyUlJY8fP75z586ePXuio6PBovyZbDYbi8UaGRnNzs42NzevXbv2ypUrt27dio+PZ7PZ2dnZAgICnp6eAAAikejm5iYrKxsREZGXlycvL29tbQ37TA8fPhQQEGhtbZ2cnPTy8tLX109MTMzPz+fh4YG+zaamJl1dXUTYCgoKdu3alZaWBnMC6OnpiYqKmpmZ2dvb5+TkUKnUdyceoPw1QYUN5W06OztFRUVXrFgRFha2OC2Im5vb119/vXfvXkNDw7CwsFu3bq1evdrc3JxCoeBwuI0bN548eXJ4eLi6uvrMmTOHDx/OyMhgMpmurq4//vhjdnZ2aWmpp6fnypUrZWVl4TCJra0tLy8vbMLKysq++uorJycnHA6XkJCwY8eOyMjI7u5uR0fHHTt2ODg44PH46upqZGEwWVnZx48fI8VraWlxdXWFPj0AwPz8vIWFhZSUVFtb2+7duwUFBeHCZqKiopcuXerr66uqqoJiCQDIzc29fv16f38/BoMRExOrrKyE25OTk2/cuAG1lslk+vr6fv31162trXNzcxYWFl9++WVQUBBSObAxxeFwJ0+evHz5cmdnJ9ze3d2trKzs6ekJFaW8vPzatWvp6elQIRoaGjZv3pyamgoAwGKxMjIyISEh4J8pYFJSUtasWaOkpIRMHrC1td2wYcPz58/hv3D77Oysi4vL7du3EXu3rKxsbm4OAFBaWiopKRkQEMBms93c3AQFBWEwZ2ZmJmLyhoSEnD9/vrS0FAAQExMjIiJSWFhIJpOrq6uRuzt9+rSjoyP498TQRCLR1NSUQqGw2Wx9ff0vvvhCTU0NhsUWFBQcO3bMxsYGPpqdO3d6e3vDQy5fvmxiYgKDTeLi4qSlpfv6+srKynh4eKAhm5GRsXr1avgoOzs7DQwMELEvKys7d+4cMp6nr69vamqalpa2OIwITV2NAlBhQ1kMbBH6+vr8/PycnJxycnIWrzCZk5NjbGysq6srKytrYWHh7e3t4eHh4+NDJBJLSkoUFBTs7OygkVdTU6OjowOVo7y8XEhISF5e3tPTMzw8XF9f39raur+/n0QiOTs7i4qKpqenAwB6enquXr0qIyOTm5vb2toqJiYmKysbGhrq4eEhKyvr6enZ0NAQHh7u5OT09OnTkJAQR0fHlpYWpAkbGxszNTVVVFQMDw9/8uRJYGCgq6vr69evFxYWzMzMzp8/r6Ki4uHhYWRkJCMjU1ZWVlBQIC4uHhYWFhIScv/+/bS0NAqFMjAwICsra2Bg0Nzc3N/ff+/evWPHjrm7u09OTrJYLAwGIyAgYGdnFxgYaG1tff78eX9//8VJk6EavXz58tq1a+rq6jY2NoGBge7u7nfv3oVmHwzFPHLkiL29PfTfMplMYWFhW1vb8fHxZ8/6XSwtAAAgAElEQVSeHT582NHREYl37+vru3nzZk5ODjJ5oL29XVpamp+f38HBwdnZGcZKlJaWXr169fr16+Xl5UwmE4/H8/HxycnJxcTEPHjwwNXVtb6+vqWlRVlZWUJCAk6uwGAw/Pz8N2/efP36dXZ2tpSUlIKCgo+Pj7GxsYCAQHh4+NDQ0MWLF11cXCIiIiIjIw0MDPLy8sAi2RgaGtLT07t48WJFRQWXy+3p6bl06VJSUhIsJIzbvH379szMTEdHBw8Pz/nz5w0MDB48eACvi8Phent7NTQ0Tp06VVRUVFNTs2XLFuh8VlJS2rFjR3Jy8sTERGBgID8//4MHD6AtjsViT58+fefOHTj74sCBAxISEnZ2dpaWlmZmZrGxscvkdkH5S4EKG8q/WCbhE1gUo9Hc3AwFDAAAV5QeGxvr6uqC/jfkDNDfyGAwSktLw8LCoOOLTqe3tbXNzMwQicSuri4YlQcAYDKZDQ0NUVFRXV1dAIDa2trY2FgsFstgMGDjODw8jMVi/f39vby8goODkQJAOBxOdXW1r6+vr6+vl5dXVFQUEq4yOzubnJzs5+dXW1tLoVCqqqqamprweHx0dLSPj4+vr296ejq0bwAAr169cnd3x2Kx3d3d8fHxwcHBiYmJMPCBw+Hk5+cHBga+fPmSTCbX19eXl5cjkevcRSuLVlVVubm56enpOTs7p6SkINlYRkZGEhMTg4ODEf8tk8l8+fJlUlLSyMhIQUGBn59fXl4eMh5JpVL7+vpgximkVnE4nIuLi6GhoYODQ2FhIZwA/uTJk/Dw8MrKSgaDMTEx4eTkZGlpGRAQEBwcDBO7tLS0BAYGRkVFYbFYNps9Njbm5eWlpqZWVlZGJBKjo6NVVVXd3d0xGExKSkphYeH09LSrq6ubm5ufnx9MQIPMJkRE18DAwMvLq6qqCupuTU3N8PAwAKCxsfHx48ePHz9OTU3F4/FkMjkiIkJFRUVWVjYxMbGoqCghIWF4eLizs/Phw4e+vr5YLJZIJD59+tTY2NjBwSEvLy85ORmLxY6MjERHR7u6uiJ1AqXO19d3ampqYGDg9OnT/Pz8srKycnJyZ86cOXfuHHTqosKGggobyr+xvLZ9+Ek+6qjf2BItdfjHdt6X2fk/nuc/ju68+9PyOy/+lbuIjy3Y78iH1Od/rzyLzwxzCHh7e8OYGgAAkUg0NjZ2d3f/L10d5c8FKmwoKCh/MmZnZ7W0tGJjYxFXeVNTk4uLC/SFoqCgwoaCgvIng0qlPnnyRFFRMTIysrm5uayszNDQMCgoaLHPHOWvDCpsKCgofz44HE5qaqqZmZmenp6lpSWce/f/ulAofxRQYUNBQflTwmazKRTK/Pz8wsICsizc/+tCofwhQIUNBQXlcwAN9EdBQIUNBQUFBeWzAhU2FBQUFJTPClTYUFBQUFA+K1BhQ0FBQUH5rECFDQUFBQXlswIVNhQUFBSUzwpU2FBQUFBQPitQYUNBQUFB+axAhQ0FBQUF5bMCFTYUFBQUlM8KVNhQUFBQUD4rUGFDQUFBQfmsQIUNBQUFBeWzAhU2FBQUFJTPClTYUFBQUFA+K1BhQ0FBQUH5rPh0YXt3Tb+3FvpDF/1DQUFBQfnf83tabO+uYItqGwoKCgrK/5hPFzYOhzMxMdHS0kKn05GNDAajuLg4NDS0rKyMSCSiwoaCgoKC8j/mU4QNytX09LS2trasrCyJREI2zs/PP3r0aPfu3Tdv3uzq6vrAExKJxP7+/k8oybulYjAYU1NTDAbjN54NBQUFBeVPyicKG4fDycrKWrFixddff93c3Iw4IWk0Wk9Pz4ULFw4ePNja2vruge+ebXx83MHBwdzcHP7L4XCW92dyOBxk+1s/USiUmJgYS0tLHA73CfeFgoKCgvIZ8ImuyPHxcXNz882bN69cudLe3n5hYQH5iU6ny8rKnjx5EofDkUik3t7exb8CAGZmZoaGhiYnJ6lUKgDg9evXmzZtOnbs2OJ9EJlE/Jw0Gm1qaopCobxVEg6HMzMzQyaTAQCTk5OSkpJbt26tr6//tPtCQUFBQfmz84nCVlNTo62tHRAQ8I9//GPPnj0DAwPITzgc7vz584cOHXr8+LGxsfHly5c9PDz6+voAABwOp6ys7NmzZ1FRUY6OjkVFRQCA9PT0DRs27N69u7CwcGRkpKOjo6ioKCwsrLy83NfXNzMzc3h4uLKyMjQ01MLCwtfXd2hoCDHUBgYGIiIiHBwcHB0d29vb+/r6hIWFN27cGBAQMDIy8lvrBgUFBQXlT8inCBuDwYiPj/fx8SGTydLS0t988012djbiIezp6bl06dKaNWuEhIT27du3Y8eOlStXSktLj46O4nC4EydOGBkZYbFYHR2d0NBQAIC7u/tXX33197///cKFCy9fvvTy8tq4ceOKFSsuXbq0f/9+c3PzlJQUc3NzdXV1YWHhr7/+WkNDg81mAwAaGhrU1NT4+flv3Lixdu3awMDAioqKTZs2/e1vfzt16lRmZiYauoKCgoLyF+RThK2ysvLGjRtOTk7Nzc0ODg7fffednp7e7Ows/LWnp0dISGjPnj1FRUU0Gq21tfXQoUOrV6+OiorKzMxct26doaFhd3d3VVVVT08PPBsPD8/x48epVCqLxZqfn1dXV1+xYoWdnV1OTk59fT10SE5MTCQlJUEDkc1mMxgMVVXVo0eP1tTUMBiMR48eZWVljYyMCAsL79q1q7CwEIofqm0oKCgofzU+VNiQSA0qlers7Lx69eqtW7fu3Llz69atX3zxxebNmxsbG+GePT09586dO3nyZGdnJwCAwWDcv39/7dq1OTk5w8PD/Pz8a9euXbt27YULF9LS0lgsVl1d3c6dO0+fPg0PZzKZurq6X375ZU5ODrzi3Nxcfn7+/fv3FRQUVq1axcvLCwAgkUjbtm07deoUDKdkMplMJnNiYkJGRmbPnj3IGBsqbCgoKCh/NT5a2MrKyqAXsa+vD4fDYbHYffv2rVixwtPTEwaJwDE2RNgoFIqHh8eJEyeGh4dZLFZbW1tQUJCoqOi333574sSJ+vr6pqYmHh6eU6dOwQsxGAwdHZ0vv/wSjsABAJydndetW+fs7FxTUyMpKblv3z4AwPz8/ObNm48fP744AHJ8fFxCQkJISIjFYoH3hU2ioKCgoHz2fJwrcnx8XF5e/tKlS3Nzc8jGR48efffdd+fOnYMaA4Vt8+bNL1++BAC0trZKSko+ffqUQqFUVFTExsb29fWNjY1du3Ztx44dra2tUNgOHDgwNTUFAKDRaJqaml988UV+fj4AgEgkiomJrV+/Pjc3t66u7tSpU9AVSafTL1y48Le//S01NXVx8a5fv3706FEYOYIKGwoKCspfkI8QNgKB8Pjx47Nnz166dCk9PR1uJJFId+/e5ePjExQUfPr0KYlE6u/vFxYWXrFixZYtW06fPq2np/fixYv5+Xkul1tSUnLgwAF5eXlzc3MJCYnQ0FAajTY2NqaoqAijRd68eRMTE/PTTz+tWLHCzMwMj8czGAxdXd3/+7//O3ny5M2bNzdv3rxq1aoXL16w2eyKiordu3dv3rxZRUUlICCgt7eXTqfr6OisWLFCRESktrb2v1NjKCgoKCh/aD7CFUmhUNra2mpra+vq6nA4HJLpo66urr6+vq6urquri0ajUSiU169fv3z58vnz53FxcZWVlchctLm5uezs7Nzc3IKCgtraWui6ZDKZOBwuLS0tLS1tYmKivb09IyMjMzMTi8XCWWvd3d3p6enJyckYDKaoqCg3NxfJaZKXlxcQEODr6/vq1SsikQgA6OrqSk9Pz8jIGBsbQy02FBQUlL8gv2d2/0/g3TwjH3iVxdupVCqcbIBMOUD2QYUNBQUF5a/Gxwnb8jLzgSry1s6L5efDdWipRXNQJUNBQUH5i4MuNIqCgoKC8lmBChsKCgoKymcFKmwoKCgoKJ8VqLChoKCgoHxWfG7CxmAwhoaGcDjc+Pg4jUZbWFgYHR0lEolUKpVCoYyMjAwNDcHlcv5QsFgsMpk8NjYGJy2goKCgoHwyn5WwcTicgoICGRkZDQ0NKyurgICAwMBAKysrPz+/4ODg0tJSV1dXFRWVioqKd49ls9mdnZ1zc3O/S1wli8X6qPPMzc0VFxcrKSlFRER82hUZDEZfX9/ijDAo4L+ZLBSPx3d1dSG5vz8KBoMxMDAwNDT0Ue8Jk8ns7+/v6ekhk8n/cZ7M/x4Yk0yj0fB4PB6Pp1KpbwU8L/6bw+GQSKTx8XESiQT//d0Lw2azCQQCHo+nUCi/8fywhPPz89PT0/CRvbXc8bvPgslkUiiU6elpOBlp8f40Gm1mZoZAILDZ7D/gc/zd+X9yg5+VsJHJZAcHB1FR0bS0NFtb2++//37fvn3u7u6mpqYHDx5MSEhITEy8evVqbGzsu8cuLCxcvny5tLT0N5aBy+XOzc1VV1fDtU8/nPLy8p07dyIriX8sIyMjoqKiGRkZv3sb8VvgcrnQGGUymXALi8UikUjInP3/EhwOh06nM5nMZT4q2Dyx2exP+/AiIiLWrFnj4eHxCceOj4+rqKicPHlydHQUfPCXX1BQICYmJicnBxOO/zEbxPb29nv37mloaBQWFgIAFhYWGhsbOzo63pJwCoWSlJQkLS396NGj/1JJyGTyo0ePFBQUMjIyfvv7RqFQIiMjNTQ0kEeGx+NnZmaWEqepqamsrCw1NTXYpCBfJZvN7ujocHR01NXVhb2iP+Zz/Fi4XC6JRJqamoIdmrd+pVKpY2NjsBPzvynPZyVsCwsL1dXVNTU1TCazo6NDRERESkpqaGhoZmbm8ePHGRkZxcXFOjo6kZGR4J3Z3ACA4eFhMpmMVP2H96bhyw3/plKpycnJhoaG4+PjH1V4FoslISGhp6f3UUchLCwsPH/+vK2tDa7X88eht7fXxMSkuroa/ovD4e7du1dWVvZfvejY2FhoaGhdXd3yMg9bn09bkxaPxx8/fvzTOiIsFqusrGzLli3d3d3gw5q2sbExVVXVoKCgsbExGo32h20NR0dHzczM9u/f//jxYwBAb2+vurr6vXv35ufnF+9GpVILCwsPHz4sLy//u5cBmSmbkZGxdetWd3d3mOTot0Amk+/fv79x48bm5ma4RV1d3cTEBJ753cfBYrECAwNXrVoVExPz1k94PN7IyIiHhwc2EX/YR/mxBAcHy8jIYDAYAABM54skoy8qKjp27NjTp09pNNr/pjCflbDBDjj8e2xs7ObNm2pqanDUikajkcnkxsZGAwOD4OBgHA6XkpKCtLYAAAaD8fr165mZGfhvR0dHampqQUEBXPv7vcA3EofDpaam5ufnwzRjFAolPDxcUVGxr68PuiDggB8sHovFgv07xH3B4XDa29tfv35NIBAkJSUNDQ0BAAsLC0NDQ3g8Hu4Mz7NYPheXAe7AYrFoNBqTyYT7QFcMi8WCFsl7vT2wAHA3WDDw73YMchKkpYAleetTRE4O7bPFZQAAVFVVbdmyJTo6Gj6a0tJSBQWF3NxcsKgBguV892xv+XAW1wBSjfBf5Ce4BYvFnjlzJikpCX5aSzl8ysrK9u3b9/Lly8WV8+FmnKSk5FvCtrj//t7iISXs7e3dsWMHkhwOLNHAwY0sFisoKEhMTKyurm7xr4vv68OdWh+VD+EtX+J/PJbNZkdFRZ04cQKaYtDpOjIyAt+ixRXCYDAMDAzExMSWuu5772iZ23zXJTg5OamgoODn5/exLvr3vuFNTU2bN2+Oj4+Hj/LFixdFRUWL35y3jsrOzl6/fn14ePi7p8JgMNu3b1+qR7XMDb77Fb+3AB/4MrzXibr4Wh8lut3d3WlpabCvVlZWpq2t/eLFC/gTHo8PCQnB4XBvlfY/vk6frPqflbAtpr+//9atWy4uLovf6fb2dnl5+aNHj6qrq4uJiR09etTFxQUAQKfT9fX1d+zYAVMnJyUlWVtbx8TEGBkZqampQefDe8nNzVVVVbW0tNTT07tx40Zzc/PMzIyWltb69evV1dUjIiIsLS337dtnbm4OZVVCQuLs2bMhISHw8KmpKXNzc2VlZT09PWFh4dWrV9vZ2QEAuru71dTUDh48aGNjw+FwmEymhYWFoKDgW+0ahMvldnR0GBkZCQsLJycnM5lMPB7v4uKio6MjIyNjamoKtfm9rwidTg8ICNDU1FRRUREXF09KSgIAdHZ2GhoaCgsLBwcHKykpHTp0yMDAAK5791brtrgMJBIpJSVFUVHx0KFDMjIyNTU1AAAKhfLw4cNvv/3W1NS0uLiYSqX6+Pj8+uuvDg4O9fX1s7OzHA4nJSVFTExMRkYmJycHADAxMeHh4WFubp6WlhYUFKSvrx8fH08ikaqqqvT19T08PHp7ewEALBYrPT3dzs6usbExLy/PzMzs0aNHw8PDsDyFhYWnTp2ysbGBq90u9QEnJiZ+//33UVFRnZ2dUAJbW1vd3d2trKwyMzP/Y2v4lrB1dHS4uLjY2tpiMBjkcnQ6vby83NnZ2cXFpaqqCvGJdXR07Ny5E7YC8/PzVVVVQ0ND7324AAAGg2FiYmJkZITcIJvNbmpqioqKSk9PhwfCNaEqKipoNNrk5GRjYyPSS3svb968ycnJef36NYlEWma3np6esrKywsLCtrY2JpNJJBKrqqpqa2vhydlsdmlpaUFBweKeeFJSEh8fX1BQELJlZGQE8UUDAEZHR+HL4OzsLC4u/t7rLn5kg4ODGAxmYmICqRAulzswMMBkMoeGhjAYDFwYZHFDPDIyUlZWlpmZKSMjExgYuPyj5HK5/f39MO5saGiIwWDAW2tpaUFS2gIAxsbGdu3aVV5ejnRNJicnkZPMzMxgMBj4ckJKSkq2bt0aHR1No9EaGhrweDzyU3Nz865duxYLW0tLS0tLy/LLIyN1Mj09XV9fv7hC2Gx2SUlJYWHh4gcBxzsZDAaZTO7s7IRGM5vNrq6uRl6kxddisVjDw8MDAwNv/UShUGpra5uamuA3guzc0NBQXl6+eCM8PwAgKytLSEgoODh4ceEX74bH40tKSurr69/rJcZisW+p4Mfy2QrbwMDArVu3nJyc4DsNq7W1tVVaWlpLS6uioqKyslJPT2/fvn14PJ7NZufl5f344495eXkAAFlZWTMzMzKZXFdXl5SUtFTHanZ2VlpaWlJScnBwsKGhIT4+vq+vb35+3svLS0hIKCkpqb29vbKycu/evUJCQqOjo9PT0w8ePODh4TE2NgYAkEgkTU1NBweHkpISLBbr5OS0evVqa2tr+NOTJ0/279/v5ubG5XKZTKajo6OFhcXg4OBbZYDv+uzs7PPnz//2t789ePCAwWB4eXlpa2tnZWVlZ2c/e/astbUVLPG1DA4OPnz4MDIyEoPByMrKnjlzpqOjY3Z2NiQk5IsvvpCTk0tOTo6OjhYQEDA2NoYfw1IikZ2d/eDBg9jY2MTExMuXL4uLi8PgCE9Pz3Xr1rm7uycnJ8/Nzeno6GzatMnExASLxQ4MDHh6eioqKubl5YWHh9+4cSMiIqKzs9PU1HTt2rWCgoKOjo4mJiaCgoICAgLq6uouLi6ysrLi4uITExNcLjc2NnbHjh379u2zsbEJDAyUkpKSkZF58+YNACAmJmbv3r0yMjJRUVEwlfa7ZWaxWMHBwd99952mpmZaWhqNRouJiVFRUQkMDMzJydHU1DQ3N1/enywhIQGFjcViJSQkKCoqxsTEBAYGampquru7wxfPwcFBXV3d09Pzzp07Fy9etLGxgQ1cV1fXrl27BgYGuFyuvb29gYFBR0fHe6/C5XKbm5uFhYX379+vpaVVWVkJAHjx4sWdO3eePHmio6OjqKjY1tZGp9PDwsJOnTrFz89/6NChixcvwj3fhUKhGBoaWlpaBgQESEtLu7q6EgiEpe6xqalJVlb21KlT2dnZ0P2grq6upqZGJpPHx8fNzc1dXFwsLS2vXLmSlpYGKzkhIeHMmTOhoaHz8/P+/v7S0tIODg5QHuh0upeXl4qKipaWlrS09M8//6ykpLRMDff393t6eqqoqIiJiYmJiaWkpHC53Ddv3ujr6585c0ZZWdnIyAi+HsnJyfCQ8fFxNzc3JSWlW7duHThwYO3atb6+vksNeHM4nPLycmlp6VOnTpmZmfHx8UlJSQ0MDNTV1WlpaZmbmxsbG+vo6EDDenBwcNeuXfAxBQYG8vHxJSYmAgAIBAJ8/WRlZQUEBAwNDaG6YDAYHh4efX19Nze3a9euiYqK+vv7w8a6oaFh586dsMc8OTnp5uamoKCgoKCgp6dXXl6+TIUAACIjI9XU1BQVFW/dugV7oh0dHUpKSiYmJm5ubsrKyomJiVwut7a2Vk5Ojp+fX1FRUVNT88KFC9LS0snJyffv31dSUjpz5kx0dDSTyZyfn/fw8JCXl7ezs7O0tBQVFT1w4IC9vT18JRYWFiIiIlRUVGxtbdXV1TU1NZuamgAAw8PDLi4u9vb2hoaGKioqQ0ND2dnZ4uLi6urqbW1tAAB7e/vVq1efPXs2LCystbVVRkZGUlISsRBycnJu3bplYmJiYGBw69atqqoqMpns7u5+9epVHR0dWVnZy5cvX7hw4cWLF2+pJvhgG+6zFbbBwUFpaWkVFRXYjsDqaG5u1tDQiIqKgvvk5uZu3LgRWdF037590EUmIyPDw8NjZWX16tUrGo22VMdhYWFBSEho/fr19vb2ubm58G0mEomurq6amppI4P6NGzcuXrwIu9WNjY0XL160trZmMBh5eXknT55EVh4fGRk5cuSIqakp/Hd6elpfX19GRgYW3tnZubW1dZmHOjU1tXXrVj8/PxaLde3atUOHDmVmZjKZTDabTaFQ3uvE4HK5RCJxbm6OSqVOTU0ZGhpu2rQJjn719vZu27YtJSUF7mlpaXn06FHEf/iuo4bL5fb09CA9ACkpqR07djQ0NAAAcnJy4OJ84+PjTCYzKipKTEwsPj6eTCbHxcUdPXr07t27Y2NjBQUF+/fvl5OTGx0dTUhI+P77762trXt7e4eGhm7evPntt9+Gh4cTCIS4uLhNmzZB2258fHzXrl2SkpINDQ0kEqmgoODMmTO6uroAgLy8PF5eXk9Pz/7+/qUGHTkcTlJS0k8//fTixYuhoaHu7m5BQUF3d/fp6WkAQGRk5IkTJ3x8fJaqcACAhISEmZkZAACHwxkZGd27d49CoRCJxIiIiF9++SUmJiYrK+v48eNubm4TExNdXV13797ds2dPdHQ0ACA3N/fnn3/OyMjw8PBwc3MrLy9/axRqMaOjo3Jycvv37/f19R0YGMjKypKVlQ0ODh4fH09PTz948KC0tDS02H788cdffvnF1dU1KSlpbGzsvWejUqleXl5lZWXj4+M+Pj7S0tKwP/deSCSSnZ3dunXrYLFxOJydnd3Dhw+5XO7U1FRgYGBbW1tbW9ulS5e0tLRgxwsK2+PHj+l0elZWlpiYmKqqKhQ2BwcHBweHly9flpWVhYWF8fLy3rp1a5kabmxsTExMzM/PLyoqUlRUvHz5MgBgeHjY0NBwxYoV5ubmBQUFqampwsLC2trac3NzeDze29tbTU0tIyOjoKAgJCRkx44dyBrI7wJtNXt7+y+//FJZWfnJkyeBgYG5ubnKysrKysr19fXl5eXXr19XVFQEAIyNjfHw8MAFICsqKn7++WcHBwcAwNDQUFhYWHh4eElJyb1793744YecnBw2m11WVrZ9+3Z1dfVXr16lpaVpaGgcO3aspKQEAJCWlsbDwwNNLisrKzMzs4KCgtLSUkVFRW1t7WXm/AQHB8vKyoaGhubm5rq7u4eGhg4PD+vp6SkqKpaXl7e2tt69e/fgwYO5ubkjIyP6+vp/+9vfJCQk0tPTvb29f/rpp8OHD0dERLx69crIyEhaWrqxsZFOpyckJGzbtu3UqVOZmZkJCQmOjo7nz58PCwsjk8lpaWni4uLu7u6vX79+9eqVuLj49evXa2trQ0JCZGRkmpuba2pqPDw8xsfHOzo6tLW1jxw5ApfhfPTo0ZkzZ+7fv19bWzsxMeHt7f3111+3tLQAAJqamqSkpPT09Kqrq0tKSm7dunXjxo2urq7k5GReXt4TJ04EBgampKQYGRkpKSm9fv363Ue2zAuD8NkKW39/v4KCwoMHD2B7AaujpqZmsbDl5eWtX78e9nqoVOqePXtg243FYk1NTcXFxc+dO2dqarpUAwEAKCoqkpWVPXz48OnTp1VVVauqqubn5318fFRUVJBWXlxc/NKlS9Dcqa6uvnjxoq2tLYVCefr0qYSEBLIbh8ORkpIyMDAA/xxPev78+cGDB1tbW0dGRuzs7KAzcJn73bJly8OHD5lMZmZm5s2bN/n5+YWEhPz9/aGwvdd/CABIS0szNzePiopSVlY+cuRIVVUVAKCnp2fXrl2Ic8zLy0tNTQ0aQ+8dY4NbMjMzXV1dnz59eu3atcuXL9fX18Nb3r59OxQ5AEB+fr6ysjIMFbO1tf3mm29UVFT09PQ0NDQ0NDRga4jD4Xbt2pWVlQUPsbS0PHnyJGwFuru7r1+/HhcXB386cuQIfHwQMzOz8+fPIxdd/NN7KS4u3rZtG/x4CgoKxMXFkdCAwcFBfn5+CQmJZQ5HhC0uLk5AQACJiJmYmNi6dau1tbW5ufm5c+dgWwYAKCsr279/PxxGra2tXb16NS8vr7KyMvIOLPXRcjgcCwsLUVFRaDro6+vz8fHBv1kslrOz8+rVq2HM1N69e/39/Ze/a0h7e3t0dLS6uvqZM2eeP3++zJ7j4+MXLlywt7cHAOTk5Li7uyOTHEgkUnd3d1RU1MWLFy9cuIDFYsE/hQ2Osc3MzJiamurq6pLJ5JGRke3bt2dkZCBnNjQ0XKqG4UsFh41HR0fh0zl+/Dj8NTY2duPGjfCFBABA07OpqQmLxUKTBW5nMBjnzp178ODB8vuEmEIAACAASURBVCHKU1NTO3fuzMzMhP9C34mcnFx0dLSfn9/Ro0d/+eUXWA87duxAOgHXr1+HwkahUGg0GoPB6Ojo8Pb2/uGHH0JCQlgsVnl5+datWx8+fAj3b25ulpWV9fT0ZLPZnp6eMHikq6uLh4dHXl4+Pj4+Li5OSEjo0qVLS419zMzMLI5XglVaVFT066+/IstPEggEAQEBBQUFAoHw8uVLSUlJ2KYtLCxA6xaqZlVVFS8vLxwDGxkZUVJSQk7LZDLt7e319fVHRkaMjY319fVhVw8AEB4e/uuvv4aEhHh5eW3dujUxMXFiYgJ6RAAAtbW1qqqqUPhzc3N1dXWRr4lIJO7evRu6EPz8/BQVFaHlBwDIyck5evRoeHj4zMyMtra2m5sb3F5dXS0nJ5eVlYXH4728vKBzCxm0+498tsKGx+O1tLRCQ0OhDxc2GampqdeuXUNqJycnZ+PGjdnZ2fDfffv2FRcX0+l0EolEpVLb29tdXV0FBQXfjWuCzM7OEonE/v7+oqIid3f3I0eOWFtbk8nkyMjI27dvQ78/AAB6IeC/MFrB3t6exWLFxcUdOXIECR+YmZk5f/48bChhaYeHh5WVlRUUFMzNzYuLi5f6OOHOo6Oj8Cui0+kMBqOxsTE4OFhXV/fs2bNeXl5L1VJkZOSFCxdsbW3b29tDQ0OvXLkCX77e3l5kBAgA4ObmpqqqCoVqqSHllJQUcXFxCwsLDAbj7+9/+/Zt2MxVVFRs3bq1qKgIHvX8+fObN2/C0CloCri4uMTExCQlJbW0tMCvrrGxkYeHB3lMRkZGIiIicFp9e3u7oqIiVCwul3vw4EH4IcF20M7OTlZWFgCAwWA2bdpUWlq6fP8Og8GsXbs2KiqKwWCkpqYKCAgg8UTDw8OSkpKqqqrLHI6MsT148GDdunWwfgAABAJh9+7ddnZ2BgYGV69eRZxLpaWlx44dU1NTAwCMj4+vXbv28OHD165dKy4uXvwo34XBYBgbG0tISMCWQkFB4dSpU8gwSVlZ2YYNGwoKCubm5nh5eX19fZePbieTyTExMdbW1iEhIVZWVleuXPmP7YWtra2amlpfX19kZOSDBw/gxomJifv373t6ej5+/FhUVJSPjw8OrEJhg2NsExMT9+7d09fXJxKJhYWFGzZsgMIA/QcODg7LjLEBADo7O93d3S0sLOLi4tTU1E6ePMlgMLhcblhY2IYNG5AKDw4O5ufnz8/PT01NvXLlCrJ9ampq//79rq6uywtbfX09Dw8PtCcAACYmJt98842mpmZkZOSTJ088PT0TEhIAAENDQ7t27YKOfQDA5cuXHR0d4b3k5+dbWVk9e/ZMW1t7zZo1ERERUNi2bNmCdKOnpqbc3d3d3d3ZbLavr+/OnTuHh4ezsrLWr18vKipqamrq6en58OHDjIyMpUpbV1e3ffv2wMBAsOhVyc7O/vnnn5FPFQBgbGwsJyc3NDQUFxdnaGgIfadzc3NPnjwxMTGBOpSXl7du3To48amjo8PExARGsQIAqFTq8+fPtbW1e3t7BQUF79+/j9i7WVlZ/Pz8Dx8+7OjoUFBQkJSUFBAQsLa2ho3Y69ev1dXV4ff48uVLNTU1xBk+NDS0fft22H9ycHBwcXFBRhxramqEhYWtrKwGBwd1dXUTEhLg21tVVQWN3dHRUU1NzcuXLzs5OSGdj//I5ylsBALh4cOHW7duFRAQaGxshC/B2NiYlpbWd999Z2VlBas1MzNzxYoVHh4eU1NTGRkZX3/9taenZ01Njb+/f15eHoFASE9P19XVXcpR09zc7OHh8fLlSwqFUlRUpKCg8OjRIwKBYGFhwcfHV1hYCB3EEhISBw4cKCwsfPPmjZ6e3sqVK7W1tel0OhaLXbVqlY6OTltbW0NDg5aW1ooVK5SVlYlEIiwwHPVZtWrVjRs3lvJTwQadzWZjMJhvv/3WyclpYWEhLS0NeW9u3boF2/r3cuTIkR07dmCx2IaGBhUVlSNHjkDJqa2tXbt2LeImdXFx2b17N7ST3mv8TUxMHD58+Pz5852dnZOTk4aGhuLi4rAJqKioWLNmDWITPH78GBn+CQ0N5eXlDQsLQ84Dx+1zcnJ+/PFHZJV2MzOzs2fPwiGr6urqAwcOwF4/h8M5ePAgMqW9sbFRX18fFvLVq1dbtmxZ3saFu23fvr2npweW89tvv0U6MS0tLRoaGrARWQoJCQloxyQkJOzduxc66wAAeDz+p59+8vf39/T03Lt3L2J6YjCYw4cPw9awp6dn9+7dMGmAuLh4Wlra4vAKBMSBbGVlZWJiAm3ou3fvwk4Y/CklJWXfvn1wUGTv3r0+Pj6wGt8rk2w2Ozc3d8OGDXBgH4vFKigoQGFbJgoOi8WqqanduHEjLCwMtmKzs7MeHh58fHxQtm1sbGRlZeH4SkpKioCAAGwo6XR6ZGSkiYnJ3NxcSkrKDz/8gHxNNBpNQUFBSkpqqeqFg9CCgoLp6elcLjckJGT37t04HA4AEBMTszjyHo7kNTU1paSknDlzBk6hAwCMj49v27bNzc1t+WRDSUlJW7ZsaW9vh/86Oztv3rwZGbRDmJyc3L17N7Lb1atXoXmRm5srLi7u4+MzPDycnJy8YcOGyMhINpsNhQ2ZNVtZWWlsbAyzQ8TFxe3atWtiYqK0tHTt2rVBQUFvxdcs9RS2bdvm7Oy8eGN2dvaqVauQ3jkAQERExNramsPhJCQkGBkZQWGjUCihoaF37txBhO2nn36Cpm1HR4exsTEibEQi0dTU1NnZeXR09NixY4qKikhjkpiYKCQkBL/lycnJ7OxsGFz29OlTJpPZ2tp6+/Zt+NlmZGRoaGggJvXExMTOnTtfvXoFALC2tlZVVUVGlCsqKvj4+Pz8/IaHh1VVVWNjY6GwVVZWampq5ufnMxiMnp6ej5099XkK2+joqLW19Y0bN/T09LBYLGwdcDicm5ubvLy8j48PbCBaWlpu3rzp6ura1dVlZmZ248aNkJCQmpoad3d3Ozs76G4OCgpaapCmp6fHyMhISkoqICDA09PTycmpr69vYWEhLCxMXFw8ODgY9rz8/PzExcXd3NzCw8NNTExERUXNzMwmJycpFIqlpeUvv/yiqanp4eGhrq5+4cIFbW3txSHgra2tsJP7VnQ7AtwyPz8fGBgoICDg6upKJBItLCx0dXXj4uISExO9vLwKCgqWarAsLCz27t1rYGDg7Ox89epVfn7+p0+fDgwM+Pj4CAsLZ2ZmwiYyNjb24sWLyzR/vb290tLSgoKCzs7Obm5u/Pz8fHx8UH7evHmzdetWLS2t169fM5nMxMTE/fv36+nptba24nA4HR2ds2fPent7P3r06MWLF/39/aOjo7BT4u/vTyAQWltb5eTkfvnlF3i2mpqa9evXw/F5Lpd75MgRISGh1NTU+Ph4Ozs7ODAAAHj9+vXu3bvv3LnT3t6+TGxVUVHR999/Hxwc3NXVRSAQ5OXlb926VVJSUltba2tra2lp2dHRsVSwTEVFxcaNG8+dO9fW1jY8PKypqXnq1KnKysq6ujo3N7cLFy7U19fX19fv3r1bSUmpqanpzZs3FhYWioqKjY2NExMTdnZ2K1euTE9PZ7PZDg4O/Pz8MTEx7w4Fcblc2Pfn4+MTEBCAJlF1dfXRo0elpaVbW1tfvnypra3t7e1Np9Pz8vK+/vprU1NTGLL43mJTKJS7d++uWLEiMDAQg8FoaGhADQZLdFmQ2tPV1V29ejW0XQAAXV1dQkJCV65cKSgoSE9PP3HihLi4eGNj49zcnKur6/r16y0tLefn55uamhQVFWVkZPr7++vq6nbv3q2qqlpTU1NfX+/o6Pj3v/9dVFR0KdWZnJzcv3+/kJBQTU1NSkrKyZMnv/vuu4SEhOnpaTs7u//7v/9LS0uD36aXl5e8vHxDQ0N1dbWQkBCsZDj8s3LlShMTk2VGrWA/bOXKlcnJyfBtz8/PP3nypJaWVnt7+8jISFtb29DQEJFIzMjIWL16dXJyMvQBHjlyRENDg06n37t3b8uWLQ0NDW/evHFzc1u5cqW7uzuNRisvL1+zZo2Tk9P09HRDQ4ONjQ0UwpmZGQcHhzVr1nR0dAwPD584cUJbW7uzs5NEItXU1LS1tS31teLxeFFR0bNnz5aUlODx+JGRkYWFhYaGhmPHjmlqavb3909OTmZkZAgLC6elpS0sLNja2l68eDE/P5/JZDY0NMjKyl67dg26jrKyslatWhUQEAAAwOFwWlpaNjY2MzMz3d3dz549k5OTw2KxNBrt4cOHv/76a2Ji4uzs7PDwsIWFhZKSUklJSXx8PPQlMplMCQmJ8PBwMpkcGxuL+LfS09OvX78eGxs7OTnJYrEKCgp++OGH/Px8DoeTmpp64MAB+MotLCx4eHhcv369qampurqal5fXzc0NSm95ebmoqOizZ8+WenDL83kK21ssIwkAgJGRESqV2tTUhHzDvb29xcXFRUVFra2ty3Sj6HR6Q0ODr6/vo0eP2tvbF+/Z2NjY3NwMw0kIBEJDQ0NhYSFU07a2trq6OiQOLTk52d7eHgawTExM1NbWTk5OImWrr68/fPgwHF56r6LALWQyubKysrq6urq6mkqlJiUliYiIyMvLBwYGQh/FUp3xgYGB0NBQJyenqqqq2dnZ7Ozs58+fV1VVPXv2rKKioqKiAurE1NTUq1evoOIu1dDjcLigoCBLS8vHjx+/evUqODgYNoJ4PN7JyUleXj4qKopKpcJW6fr167BnNzY2dvfuXT4+PiEhIR8fn/Hx8ba2Nm9vb2dn57CwsN7e3vT0dGtra1tbW9iDnpqasrW11dTUhFkMjh07xsvLa2pqCqcrIbHOs7OzXl5eV69ezcrKejewCqGvr09KSkpERAR2Hbq7u5WUlHR1dZ2cnIyMjKBJtHgu3WKePn168eLFK1euwNHy4uJiKSkpHR0de3t7JSWlwsJCOLnwyZMnV65csbGxuX//vo6ODrRvWltbNTQ0rly54u3tDWvY3t7ezc1tcUQ4Ao1Gg17iK1euQHsaABAQEHDlyhVnZ2ddXV1XV1c6nU6j0dzd3a9cuaKvr7/M5Es6nR4aGiogICAhIWFlZWVhYSEjI/Ps2TMkjP6t/ZE3Jz4+Hj4guJ1AIHh6egoKCsrLy9++fVtBQcHMzKy+vh7GL5w7d87e3r6zszM6OlpQUFBdXb20tBS64E6ePGloaOjk5CQlJXXq1CklJSVoMb8Li8VycHDYs2fP9evXTUxMbty4wc/PHxAQ0NjYqK2tfe7cuUePHkFPRkJCgrS0dGRk5ODgoIODw7Fjx27fvn337l11dfVTp07p6ektNWrF5XLr6urExcV5eXnv3buHDCaFhIScPXtWQ0PDzc0tODgYi8X29PSYmJgcOnTIxsamvb09JSXl/PnzkpKSAwMD6enp+/btU1JScnFxMTY2PnPmjLW1NZFIrKmpERERuXbtmrOz8927d/39/UdGRmBUp6am5unTp/Py8mBw78mTJ1VUVAICAuAsl6WeHQAgKytLUFBQUlLSz88vOjq6u7ubxWKlpqZeuHDBxsbGxcXFwMAgPT2dwWB0dXVpamry8fE9efJkfHw8IiLi9OnTMjIynZ2dXC63vr5eRETE1dWVxWL19/dLSUkdP37c39/fycnJxMQEmlYAAAqFIicnp6ys7Onp6eLiYmRklJiY2NDQoKamZmRkVFVVlZaWpqqq2tzcDPvTZ8+ehdZqQ0ODvLy8vLx8RUXF/Py8q6vrsWPHAgMDYSfGwMBAXl6+tLQ0KipKS0sLftoJCQmHDh0yMzODvZCmpqabN2/6+/t/WsaJv4Sw/XnJzc11dXVFM0C+FxaLdfDgQSR083dheHgYg8G0tbUhSRM+/FgymZyfn4/Mc0Lo6urKzMxsbGyEBsHvAofD6erqysrKQtzFH1XU3t5eDAaz/ES3/widTi8pKSkpKVl8X8PDw729vXNzczMzM0NDQy0tLZ2dnTByEvb8mpqacnNzYQ9sYmKiuLj43UksyO2w2ezs7OzY2NjZ2VkWi1VXV1dVVTUwMFBdXQ0jL6CwjY+Pl5WV1dfXMxgMJpNZWloaGBhYXV3N5XJhJ3WplJ4cDmd4eLi0tBSDwRQVFSGGHYfDgSGO7u7u0OFJpVLhbhgMZmBgAIvFFhUV5efnDw4O0un03NzcsLCwwcFBLpfb3t5eXl6+sLAAy+nr66ujo4OEzLBYrL6+vqKiotLS0paWFlgnZWVlDg4O9+7dKy4uXqYfBmlqarp//76Li0tOTg7sKzOZTDjIZ2FhUV5eDpVgdHS0srLy1atXjY2NIyMjzc3N7e3tXV1dExMTsKPW2NhYWVlJoVAqKysvXbp07tw5W1vbiIiItxz4o6Oj/v7+BgYGDx486OzshBvr6urMzc1NTU0DAwNhX4dIJL5+/bqgoADOPAEAYDCYBw8eDA4OUiiUkpISDAbT2NgIhY1AIISHh+vq6jo7O8OReCqV2tDQgMFgSkpKoN+C9P+x955xUSXb+rD3f+89587MmXGSIpgRdRRRTAgCgiQlK1FyzjmLgJIREBUk56w4oASRJIiSJOccm9zQNE03NE033fv9sH5n/3gREOecuWfOXJ9PsHuH2rWraq1aVet5FhZqa2vb2tp+Gx3aF8P2R8Ty8jL0+du3b6N7BL5gHWg0Gjs7+9Y7+n4bUCPxWdZiwzsAfieu23U8LJ917e9RnnW3XVuqzSb6m/3E+P8TDa+95zoC4g0rYe0lWzx67a+Mj4h11lLwrHuRdWX4+Clrj68lsllX4LV/f/ysj4u69iZoSVAnAM3v/rjmNywAHExOTr58+XJUVNTHj177CuuuAk4iOLguqrGWfGfdGgp6JoPBoFKpqBVfe5z+d2zyxbaFL4btj4iBgQEPDw9VVVU3N7dPLin/3wSDwWhrazt69ChkOPyz7rn2760HxK3vs9kI+w+W8JOP2+b5/6znri3AJ4vx8dC/RZE+vuGGN9/MnGxxySdLuOE9t7jVhk/c8I0+Wf4Nj2z9E+OjFNVPejnrLE14ePi6LJGt3+KTB7f4Cputp/yzuh6KL4btjwgsFltQUFBRUQF0R7/TgPhvDTKZfPfu3Rs3bri7u28Yy/qCL/iCT2JqasrCwuKHH36wt7f/J4bK/+X4Ytj+cGAwGDQajUKhoNP8L4ZtHaCKJiYmJiYmZmZmfm8RnC/4gj8rent7S0tLGxoapqen/8Ho3x8KfyrD9scxAIxN9pj9hvv8SwzbPx4KQO/zj99kw9v+Hnf+nW67nef+7z/0fxP/YITw3xpbxOg+69p1xz8OYP62spHJZDSS/2f6Ln8Gw7a0tDQ4OLgFkeu/EP+mbeXjwP3/BWzIFvavKsyfCf8qj+GPgE+uMG3z2u3/9AXIn8Ow5ebm6uvrb0Hk+puRmZmpra29Ge36FqDT6Vgs9pM7d//IoNFoeXl5qqqqcnJyDx48WKvQ8UkQicQXL16kpaX94wKP/5uAwaK+vt7b29vb2xvdSf/PwsTEhKOjIyglIQgyNzfn4eERFBSEsq/9iUGj0err6589e1ZXV7c1D8ifAHQ6vbGxMSMjA7JIR0ZGCgsLe3p6tmPgV1ZWhoaGPnz4sFl6H4BGo2Gx2LUJG6Ojow0NDVukov+fwnYN2/YdhO1sm1l78JMbeD5Zhq6urpycnC3aAWMNPvn0tccLCgpcXFwmJiY2PHmz2yIIsrS0ZGhoiDIjoCcw/qnY/g0RBCESia9evUpNTYVhZV2xPwadTq+vr+fm5v7LX/7i7+9PIBDwePzExERWVhbKYrUZlpaWvLy89PT0YBq9riRbY+2rbfhRPus+Hz/6kzcZHBzU1tY+cuQISrX8WdjwAyEI0t7e7uPjo6OjA3QPi4uL9+7d09XVDQgIgAT8bWJqamrDPO61wOFwBAJhO7X0vwYgR+Xj41vLofxnxerqanh4OAcHR2BgIJVKrampAdLF7VxLpVLz8vKuX79uZGS0xWlNTU2WlpZmZmaBgYEuLi6Ghoaampra2trq6urZ2dkoMfFvA7SclZUVDw8Pf3//te3z38Up+QzD1tvbm5GRkZ6eXlRUlJ+f7+/vHx8fDwmS5eXlL168gM1paHeam5t7+fJlRkbGWnb89vb2pKQklAcdTp6ZmUlLS0tOTgbGBFD8Gx8fp1AoDAZjZmamq6sLh8MxGIyVlZXJyUngVSORSKAxTSQSCQQCTPNnZ2fhMywtLfX396MiimhgbWFhoa6ubouuxVgj3Eyn0z9OYp2fn0dHFvRl8Xh8Z2cn+tVxOBwzM/N2Uqx+2+izzcF9LUZGRtTV1bW1tcHWbjMq4uzszM/PD6yyvb29FRUVKioqIiIi23kcJOF+ViF/P3xWdYWEhHBzc39SHGCzBzE+coAQBPHw8JCSkurt7QUm+NLSUhkZmerqahwOt/10hfHxcXNzc5R+cDM8ffrUxcUFJVD/lwPqpLOzU0pKytXVFSX4+LOCwWDU1tbu2bNHV1eXQCBMTU0JCAgoKytv8/LGxsZLly6dOHFii3Pi4uKkpaUjIiIiIyPFxMSA8zYlJcXMzMzJyWmt3ulvKz+CIMvLy46Ojp6enjCi1tXVPX36dOhT/Kt/EHxGKLKnp8fV1fXo0aN8fHzu7u46Ojq8vLxWVlZpaWmOjo4qKipqamogeoIgSH5+vr29vZeXl4aGhrGxMYxxBQUFHh4eJiYm2tra/v7+QNHU2dl59+5dNze327dv29radnZ2FhcXm5qaOjs7g50rKCiQkZEBFYyJiQl7e3sVFRVvb29NTU1HR8fW1lZfX18jI6POzk48Hu/p6amtrf3o0SNPT08TExNTU1MgZkX+rrns4+Pz8OFDPz+/kJCQX3/9FbiU1r4mOiqVlZXZ29snJCQwGIx37955eno+ePAgMjLSx8fH2NjYx8cHUqexWGxKSoqvr29AQICdnV11dfXi4uKDBw++//57GxubrKyslpaWlJSUx48f5+bmRkZGhoWFFRcX+/n5RUREkMlkBoNRVFR0//79tLQ0PB7f39//6NGj4ODg9PT0x48fu7q6pqWlUSiUkpISNzc3Pz+/2tpasPcIggwNDUVFRT148MDT07OiooJKpb569So0NDQlJSUlJcXHx8fDwwNluK+qquLg4BAUFExNTd1mXJFGo9nY2IiJiYFyd1FR0b1793h5eXl5eQcHBzebN9Dp9La2try8PLR3YbHY2NhYPz+/58+ff3K20d7e/vz58+fPn0P1goNSXl7e1dW1sLCQl5dXUFCwNVk7gEql1tbWPn/+HKgNUIB4LFo2Op2Ox+OhVBgMpq+vj0qlRkdHy8jIFBUVkUikvr6+8fHx8fFx8HhGR0eHhobm5uY+ZvpZa9La29vfvHmDMjktLi7euHFDVVUV/gVuTwsLi7XBaiKR2N3d3dvbu87dBucAHKzW1ta9e/eivv9m1trd3V1BQQHloUcQhEKh9PT0DA8Pry3t1hU4MjKy4ShGp9PXfsQt4qjz8/PrasnJyQk4x9cWY3R0FOV52WKq8XGB11Y4nU5Hr92OEwPS0usOTk1NoV3jH5/vcnJyOjs7Q6nMzc23UJ77+FmWlpbnzp3b4vza2lpUNcLHx4eVlRXaCZFIrKys3IwyeJsv9XGwBEGQiIgIoPxHfpNjvc3HffLgNp/7eWts+fn5LCwsAgICLS0tU1NTAQEBO3bsUFNTy8/Pf/HiBQsLi62tLZVK7e3tVVJSMjAwwOPxZWVlAgICpqamcP6vv/6KwWBCQ0OZmZlB/yIkJISDg2Nubg6Pxz9+/LihoeH169f8/Pznz58Hytd3794xMzODvMX09LS9vf3evXuFhITk5OTu3bvX0NBw+/bts2fP5ubm4nA4fX397777TlFR8e7du66urocPHzYwMAAP8fXr1zIyMs7OzlVVVVZWVj///LOSklJCQsJmhu3Zs2eHDh0SExNjMBgZGRmHDx+Gl/X39zcyMvr6669B3johIeH48eOenp6FhYVqamoRERHz8/O3b9/+5ptv5OXlg4OD3717Z2Ji8p//+Z8XLlyQkJCQkJCIiYnh4+P7+uuvYS6bnJzMxMQEClstLS3Xrl376quv+Pn5jYyMBAQEmJiYnJ2dnZycQHH4xo0bwPEzMDBgY2OjrKxsbm7Ozc0tJCTU398fExNz+vTp77//XlRUVE5OjpWVVUREBLyN3NzcgwcPHjly5M6dO9tM/ALDJiIigspSy8jIHD9+/OTJk5mZmSi/zrqqAzZCNjY2EB6bnJy8ffu2iYmJhoaGhIREWlraZoPX0tJSSUmJk5OTg4ODnJycjo5OXV0dBoMJCwsTFBSUkpJ68uSJhYWFgoKCm5vb1nRQWCz28ePHLi4u8OiYmBg8Hr+6upqcnKyrq6uoqKimpgak+/Pz8wEBAUZGRq6urhISEpqamqOjoykpKSIiInl5eQQCARSfk5KSGAwG2DxHR8f379+vW0BFuxyBQAD+T1NTUzs7O2jDVVVVp06d4uLiyszMbGtr6+npAdXm5OTkjo6OlZWVd+/e3b9//8mTJ/7+/n5+fs3NzVQqta6uLiAgwNvb28vLS01NraSkJCMjY9++fbKysq9fvwZbu+HrGxoaSkpKRkVFwTDU0tICNw8PDw8ODgb5ty0GiIGBgcTExKCgIGdn55iYGCwWCyHo5OTk5ORkPz8/qNLu7u6UlBRLS8ugoCBoDC0tLVFRUfHx8ZmZmdHR0dbW1tbW1uXl5dDFqFSqra0tatjodHplZeX9+/etrKzc3d1hftna2hoSEhIdHQ2U2QQCISsrKzMzEwI2H7c3BoNBIpHKysqePHni4eGRlJS0RbUA2tvbQ0ND/f39AwMDQbEWQZDZ2dnw8HAHBwdnZ+eQkBDQEPgYZDI5Pz8/Li7O398/KytrYWFheno6Ly8vLS0tJiYmPT0dDQVRKBQODo6EhAT418jICHVrMI95DwAAIABJREFU8Hh8VlZWVFRUQEBATU0N2nLa2tqePHkCvi8XFxcqPvcx1r7g4uLi3bt3Dx8+vJm3SqPRampqIiIiQPRgdXW1qKgoLi6uqamJTCaXlpZGRkaWlpaWl5eHhoYmJyfD8LK6ulpRUZGQkNDU1ATZRy4uLiBACsxh2zEwk5OTSUlJubm5OTk5OTk5GAyGwWAMDw+npqaWl5eXl5cnJCS0trZuZsPodDr4piBW19vb+3sZtufPn585c8bX1xf+7erqYmZmjo6Ohn8NDQ1NTExIJFJUVNTly5fd3d3T09NjYmL09fUtLS3BLx4YGCgqKoqKitq7d6+TkxOCIE+ePAFNLGjKcKvbt28LCwvDoEChUHR1dWVkZOAnLBarp6cXGRmJlqq5udnAwADifnl5eZKSkoWFhVA17u7ue/fuhT6jqqqqo6MDvIvl5eUSEhKflKEKCAgQEhKCv8PDw/ft24duJOHm5paWll5dXXV0dNy9e/eLFy8mJyfn5+eh03Z2dh4+fBgkKuBfUVFRBQWF5uZmoEuuqak5cuQIamAcHR3l5eVhYvT27dtLly5ZW1sjCDI7O3vixIkffvgBlDkTExNZWVlBP8zOzu7gwYNZWVlkMjk7O/uvf/1reHg4giBubm5nzpxJS0tDEKSoqOjMmTOWlpYIgrS2tmpraysqKqLTiE82kXWGraSkBATqzp8/39LS8rGSDjQ7KpX67t2706dPi4mJIQhSVlb2448/wvSruLg4Ly9vszgwHo+PiIhITk4mEomgMWZgYABSIOzs7Dt37vT09KyrqwsODt63b19xcfFm7KhEIvHhw4ecnJzAvPfo0aOdO3dmZGTMzc3Z29s/fPjww4cPwsLCp0+fxuFweDze0dFxx44dP/30Ez8/v4WFBRg2bm5uiPiBExYYGIggCJVK9fT0tLS0RHVT1747giCrq6sFBQWcnJwpKSnl5eViYmLy8vIYDKa8vPzIkSMHDhyws7PLy8urr6+/cOECMzOzra1tQUFBY2OjpKSkmppacXHx8+fPZWVllZSUmpqanj17dvHixZ9//llQUFBUVDQlJSUhIeHw4cMnT5709vbeItKopKT0zTffyMrKgvNubGwsJSVVVFT08uVLWVlZa2trmIpt2AAwGIy1tbWiomJWVlZYWBg7O3tQUND79++NjY2ZmZlPnTqlra0tKyu7f/9+JSUlPT09AwODo0ePmpmZ4XC47OxsPj6+v/zlL6dPnwYF5HPnzomIiJSVlQFllIODQ0BAAEz4oDDa2toODg6ioqK3bt3q6+trbm4WEhLasWOHv78/hUKZnp6WkJCQlJRENW8/Rnd39507d6ytra2srC5fvrz1UtbIyIiOjo6oqGhwcLCGhoa4uDiDwZibm3NycpKQkLCzs3N0dGRnZ9fT00PVX1EQCAR/f38lJSUHBwdVVVVxcfEPHz5UV1fr6+ubm5vfvHnz6NGjvr6+MBFcWVnh4OBAtW9QwzY/Px8aGionJ+fi4gI3Ab+zvr7eyMiIh4fn5s2bcnJyP/zww5UrV7Z4ERQkEgkM22ZTZzqdHhMT88MPP5w/fx54sLy9vf/7v//b1tZ2Zmbm8ePHO3fu5OLi8vT0lJSU5ObmVlZWxuFwq6urERERLCwsjo6OCwsLJBJJWlr6m2++cXJyWhcC2QxYLBbEuF1dXW/fvi0qKmpra4vH4+vr6zk4OM6ePXvjxg1eXl5U7GktoGXOzs66uLhoamqam5tzcnKCo7xNfJ5he/HixdWrV1GRqpaWFmZm5oiICPBenZycHB0dyWSyu7v7jh07Dhw4cPbsWR4eHjMzs+zs7OXl5fr6ektLy2vXrqmqqjIzM7u4uCAIUl1dzc3NvX//flFR0QcPHkxMTNDpdEdHR9SwIQhy7949SUlJ+Ht4eFhbWxuV7UEQpLa2VldXF7SFCgoKtLW1YQ1vdXU1ISGBiYkJxmVra+tr165lZmbCtjddXd3NOL9R+Pr68vHxUSiUpaUlNze3ffv2oR1MRkZGVVWVRCK9fPmSh4fn6tWrhoaGSUlJ0GkbGhoOHjyIcrE3NjYaGBhERUWhd25ra1tr2OBB4D/m5+fz8/ODwgXIpaqpqYE7VldXx8rKGhIS0tPTc/r06X379vn6+mZlZQUEBHBwcPj6+hIIBJjeQbccGxsTEhICkWIikRgeHm5mZoaymXyuYWttbc3Ly5OTkwOL9TEYf08SmJ6elpWVvXbtGlTFkSNHPDw8SkpK+vr61u2m+Rh4PL6xsbGlpeX8+fPKysqg5iotLS0qKgrNbHR0FJQyNpv51dTUsLOzi4qKVlRUlJSUhIWFHThwIDAwkEAgkEgkDAZTXV1tZma2d+9e4O8fHx9nYWG5c+cOGpuKiori4eGBLjcyMmJqamppaUmn00kkkpmZGapWvO7dEQSZnJzU1NS8fPny27dv29vbtbW19+/f//r1awKBICAggPrsc3Nz9+/fNzAwADfr9u3bV65cQSNLOTk5586dCw0NpdFoERER/Pz8qDtFIBAuX74Mim7I5h/R19eXn5+/uLgYQZCYmBguLi74G0GQtra2H3/8MSwsbMMtu6urq4mJiceOHUtLS+vu7m5vbxcTExMSEuru7p6amtLS0gI96ImJCSUlpdOnT8NgmpycfP78eeh0paWl3Nzc4LNC3SopKcnKykL0WF9f/+7du3g8fmxs7NKlSxoaGnBaV1eXkJCQubn50tJSVVXV/v37Qa9ycnIyIiIC/NQNwWAwRkZGpqamaDQagUDQ19dHPdENER8ff+LECRcXFywWOzg4mJubS6FQkpOT2djYUFXMlJSUI0eOBAYGzs3Ntba2trW1dXV1TUxMlJeXHz9+HOiMV1dXged+YmICArwDAwOqqqqHDh2CfYlg2NBlWtSwFRQUnD59OjQ0lEQijY6O7tq1y9bWFiSTjIyMwOcbHx8H9bstXgQFmUz29vZeZ9impqY6OjpaW1t7enoIBMLi4qKlpeXJkyehy1CpVCkpKRcXF3icvr4+Pz8/RC/z8vJAzxqalo2NTUBAAES8TExMrly5ss1QJIPBiIyM5OTkRN2v9PR0NjY2kPP28vLi5OS8f/8+VOBmNxkdHa2uroaP6+DgcOHCBVS+45P4vF2RJSUlYH7gYGdn5+7du2NiYmA4k5KS0tfXp9PpoaGhTExMIKGLgkgkXrt2TUVFZXx8nE6ny8rK2tvbIwhCJpOnp6cLCwv9/f3PnDnj6ek5Pz/v6OgoKioKfvHKyoqxsTEqSIjBYAwNDfPy8tDpHchYgHNUXFysq6sLbZRGo8XFxTExMcF9urq6pKSkBAQELCwsTExM0K6+BQICAs6dOzc/P08gEAwMDPbs2YP6cQYGBiYmJrCs2tLS4ubmpqCgcPDgQVg4mZ6ePnbs2Nu3b+Hk7OxsSUnJtYqalZWVR44cQUPhbm5ufHx8UCSIxIJhW1hY8PHx0dbWhjM/fPhw+PDh8PDwuro6FhaWs2fP5uTkFBUVvX79+t27d9PT0ysrKw4ODvfv30cXjYSEhKDqCARCcHAwaBl//GU3BI1Gs7W1FRUVRQ1bTk6OoqKihITEZpeg0Uh9fX2wfwsLC97e3idPntyzZ8/Vq1dfvHixWeukUqmdnZ2+vr7q6uoWFhbMzMxaWlqzs7M0Gk1XVxf1bEBRNykpaTPDlpeX9x//8R9nzpxRUFA4c+YMHx+fkZFRbW0tkUisra318fERFxdnY2O7dOkSjMUYDGbfvn2wgQ3usNaw0en0kJCQY8eOdXR0NDY2ogKqG754a2vrt99+y8bGZmZmZmdnJyUlpays3NbWNjMzIyAggK6yzMzMuLi46Orqwrfg5+c/evQoai/fvHnDx8fn4eFBJpNjY2MNDQ3R3Rb19fVHjx5FpSY3G198fHwuX74Mg4i3tzcrKysEAxAEmZycZGdn9/X13XCdEhyjb7/9Vl1d3dTU1MrKSkJCwsLCAoPBdHd36+vrQxuem5sLDAy0srICNyU7O3vXrl0Q2o2LiwNtObjh8vKyl5fXwYMHYX+shISEurr61NRUfn4+Kyvr3bt34TQ8Hm9tbc3BwQGWXlxc3NzcnEwmJyQkPHjwAN1b+3Gd0+l0KpU6Pj4OEUJBQUFxcfENWwWgurpaUFBw9+7dKioqMTExo6OjMzMzVlZW6urq6Ag7PDzMzc1tbGxcWlqqqKioqqpqYmISEREREhJiYGCwbiCmUqk9PT2vX7+Oj4+HdgWO48eGDaw4rL7fvXs3MzMzLi7u3LlzT548KS4uVlBQQE+emZmxs7ND3aCtAVMrVlbWtaHI5ORkDQ2NW7duWVpafvjwgUwmm5ubs7OzwzoclUq1s7NDLZampqaenh5c2NnZef36dUNDQ1Aqt7a29vf3h9MCAgLU1NQ+mfsEn4lEIhkYGFy+fBk9TiQS2djY7O3tqVRqcHCwjY0Nus69xerp7OxseXn5q1evdHV1z58/j6qcfxKfMWMjk8mJiYns7OzW1tZzc3MUCqW0tJSJicnb2xuGKh4enuvXr2MwmIqKiqtXr0J0AofDTU1NEYnE2dnZQ4cOBQUFjY+PV1RUsLGxWVhYLCwsPHv2LC8vj0KhdHZ2ysjI3L17d3Z29t69ezw8PDk5OZOTk5mZmXv37hUTE4MdzI2NjYqKiuXl5TAM0Wi0goICWVnZ+Pj45eXlp0+f3rx5Mz8/HybdkZGRO3fuBHGsubk5aWlpfX19DAaDwWBmZma23o1GpVKdnZ25ublBg8PV1XXXrl2oCig/P7+kpOTo6GhnZydsGpydnTU2Nj516hSBQGhoaNi7dy8IddLp9OfPn1+9ehW19Kurq2lpaXv27AEdh9nZWQkJCS4ururqagRBcnJyLl686O7ujiAIHo83MTFRVlaGVltVVXXw4MGHDx+SyWQxMTEeHh44DisNUBuwYgHHh4eHQTUKQZDx8XEbGxtDQ0OwB0tLSxgMZnZ2dmu5IysrKwEBAXjBlpaWrKwsTU1NTU3NT7YWCwsLYWFhBEFgvksmk1+9eiUtLX3t2rXN8sP6+/vZ2dk1NDRmZ2dJJNKlS5dUVVXBQru7u6PWdGxsTEdHJykpabMtlyUlJbt27dLR0SGTySsrK+g8LCUl5fTp0/b29mQyOSsrS1lZGSZJk5OT+/fvf/jwIXpmXFwcLy8vuvmwqalJXFzcxcXF39+/rKxsw+dCP+zr6+Ph4VFSUpqengbycjg+MjKydsY2OjqqpKSkpaUFhk1HR+f06dPojK24uJiXl9fPz49MJsfHx5uYmKALig0NDceOHfvkxnEvLy8hISEQ+fP29j5w4ABqNefn51VUVCIiIjbUZCcSiS4uLrt27UpKSmpsbCSRSNCPEATJz8+XlZWFRSM8Hv/o0SNbW1toPC9fvty/fz8kkmZlZUlJSaGGbXFx0cvL6/LlyzA5sLGx0dHRGR4efvv27dGjR11dXdHT3N3df/nlFxhDg4ODL1y4kJeX5+3tDVKTW4gRvn37VktLS1dXFxrn1oZtdXW1vLxcV1eXm5t73759N27cAAUWOTk51MtkMBgqKiq6urpDQ0MZGRmwxaysrMzGxkZRUXGt/aDT6RBQdXJyys3NlZOTO3bsGNoTT58+jYYijY2NdXR0GAyGubn5gQMHsrKyXr16lZubW1NTs7i4+O7dO0VFRVQFG9zoixcvbv2VATQaLSwsjJWVde2M7cOHD8+ePcvMzMzPzx8fHyeRSBYWFqdOnYJPSafTLSws/P39wWPQ0tLS19eHCzs6OiQkJIyNjalUKhi2wMBAOC0qKsrU1HSbSb1YLFZJSYmHhwc9sry8fOTIEWdnZxqNFhIS4uDg8MkNlrOzs3fv3pWUlIQte2JiYuhU4ZP4DMNWW1vr6OgI8nERERGdnZ0WFhbS0tJXr16FFRQtLa0TJ074+/uPjIw8fvz4xIkTioqKGhoaKioqGRkZOBxORETk2LFj4uLiBgYGJ06cuHHjRnFxsaOjo6SkZFFRUXR0tKqqKgh+vnnz5vTp04KCgurq6hoaGhcuXDh06FBycjKJRHJ1dd2/f7+RkRHYmJGREQ0NDWZmZnt7+7y8PENDQw4ODg8Pj/n5eRqNlpaWduDAAScnJxKJ9Pr1a1ZW1jNnzsD4bmpq+vTp0y14P7u6uiQkJFhZWZ88eZKWliYjI8PCwvLq1SvoThISEtzc3BkZGXp6ekZGRouLi83Nzerq6u7u7nQ6fX5+/pdfftHR0SkrK5uYmIiIiLhw4YKbmxvqJre2tu7Zs0deXj4pKcnV1fXMmTNcXFxv376FZsrGxmZjY0OhUHp7e3l5eQUFBYeGhhgMRl1d3bFjx+zt7VdXVwMCAo4cOeLl5YXFYoeGhmBTxtDQkLy8/M2bN1taWmC/2fXr14WFhZeXlwcGBmRlZcXExEZGRmg02rt37zg5OUGjcsPXZzAYBAJBSUnp2LFjRUVFNBqtvb09Ly9PR0fnxo0bc3Nzm6Wf0+n0oaEhSUnJK1eujI6OFhUVxcbGLiwszM/PP378eO0+1XVob2//8ccfQXG4urqalZVVTk5ufHycTCbr6ekJCAiASZ6YmNDU1Lx3795mXDOdnZ0XL148evTo1NTUysrK8vLy0tISg8G4c+fOoUOH4uPjyWSyjY3NoUOHQNK3tbX1559/dnd3h6+zsrISFBR05syZ6OhoCEUQicSgoKCjR49qampuJk4NR7BYrKmpqYiICHyvlZWVpaWl1dXV3t7eS5cu3bx5E3yp3t5ecXFxRUVFeAVvb28mJqbY2Njl5WUqlZqcnHz16tW8vLyFhYWQkBA1NTV0loDBYM6cOePk5ISazA1x7949NTW1mpqa1dXVuLg4aMNUKhXmxCdPniwsLNxsxT4tLW3Xrl1xcXGodw+SJfn5+TIyMuHh4QwGA4vFenl5mZiYQPd5+fLllStXYNApKSlRVFSMjY2FuVRXVxfIbi0vL9NoNAsLC1dXVywWi8fjRUREtLW1oULGx8fv3Lnj5uYGGf0TExMXLlxgYWF5/PgxeDZbZKeoq6vLy8s3NzfPzs7a2dkJCAhsUTO9vb29vb0UCgW2pQgLC8Ne5UOHDsE+DgRBGhoa5OTkQkJC4BWgBshkcmhoKAsLS21tLePvGYp9fX1XrlxRUlIC8TkDAwNWVlaYdJLJ5BMnTsDCP51O19XVVVZWZjAYISEhhw4dgj3MNBoNXh/6tY+Pz8rKyurq6sjICAQbNnuLtQCl7P3796M+LoPBoNFoIE0H9mllZcXT0/PYsWMLCwuQ2c3Ly+vg4ADehqqqqra2Ntytra1NTEzMwMAANHTMzc39/PyglUZGRhoZGaF7PVZWVubn5zfrCEtLS9bW1sePH0c7OxaLPX78OKz9+/r6mpmZfTIn4fHjx2pqaoWFhaBqe+DAgd/FsC0tLc3MzECiGA6HW15enpycnJmZwWAw8HlmZ2dHRkaAcWNxcbGysjI4ODgpKam+vn5+fh5GkKioqFevXo2MjIyOjk5MTBCJxObm5tDQ0LS0tJycHFhgg1p7+/ZtZGRkbm7u4ODgxMREe3v7yMjI9PR0VlZWV1dXS0vL8PAwlUqdnp5+/fp1Q0NDdXV1QkJCbm5ueXl5VVUV9HwikVhXV1dSUrK4uJidnS0nJ2dvb5+amhoZGampqXnhwoXIyMjNukFnZyekiaSmpj59+jQ2NjYqKurdu3dgCaqrqxMTEzMyMnx9fbW1tQ0MDNzc3FDJaSqV6urqKicnl56e3t7enpubC7vF0E0Hi4uLT548UVBQsLa2hi1JDx48aG1t7erq8vPzu3fvXmho6KtXrx4/fnzr1q27d+/m5OQQiUQI0hoaGnZ1dRGJxOjoaDk5OWNjYwsLi5iYGFiXVlBQkJWVBTtHo9FCQ0OlpaWzsrKoVGp2dvYvv/yiqKjY3d09NjZmZ2dXUlKy2euTyeSQkBBYILGysmpvb19aWpqeng4ODv7+++8lJCSAVWEt0OhBRESEtLT0rVu34uPjU1NTubi4DA0NbWxsnJycysvLNzOlY2NjfHx8LCwsPDw8Xl5egoKCx48fz8/PT0xM/PHHH/fu3QuLlEQi0d3dnZeXd8O1LgRBaDTas2fP9u/fz8vLa2hoaG5ubmZmNjw8HBMTw8TExMHBYWxsfO3atT179ri5uU1OTsrLy3/11VeCgoIQca2urhYQEPjb3/5mbW29NgZ4+vTp58+fb800RqfTy8vLz549q6mpmZGRce/ePTs7u/r6+szMTFhy/vDhA4VCiYqKOnjw4IULF2CWMDo6Ki0tzcvLGxkZmZOTY2Vl5eXltby83NraCts00EWm1dXVmzdv8vPz19TUbJEj6Ofnd/nyZUtLy+7ublgXZGdnh2ZsYmJibGy82XZwBEF6e3tFRUV5eXnT09Pz8vICAgIKCwsHBgYsLS2//fZbMzOz6enpiooKERERQUFBWHLOzc3l4uKKiIhAECQ1NfXChQsWFhZFRUVZWVmenp62trZzc3MMBqOpqUlAQEBYWBim7NHR0VeuXIGdULm5uRDmQlujk5MTKyvr1nLSAFVVVU5OzsePHzs5OTExMfHz86/NaliHuLi44OBgGK9ycnKUlJRgVFFTU1NXV6+pqVlYWNDX1zcyMvq4iurr69nZ2RUVFWtra6enpzs6OioqKgQEBAQFBd++fevl5cXCwsLKygoTkaKiIlgCZzAYGAxGWFiYl5d3bGysqakJJMWHh4fHxsZA3ZRCoaiqqkJY8vXr16ampt9///358+e3Q0kDq5j79u3bLEwHVZqTk8PMzBweHv7y5Utra+vvv//+5s2bELsCHXNo2LDNTV5enkgkjo+PKyoqWllZwbwlLi5OVlY2LCwM9p3Gx8cLCgpuRnTCYDBKS0uvXr169+5dMIH37983NDQcGhqi0WjS0tJXrlz5ZFzxwYMHwsLCsJuXjY3t+PHjaAL0J/H7UmotLCysI1WiUCjrPH3IsJ6bm/s46L+0tLQuWghxLfgbonxUKhXcxtXV1dnZWQiKgp+CdhIqlbqwsCApKenn54fH48GFb2trs7CwsLa23mzmQaFQSCTS8vLywsICLMCSyeTFxUVUD5BMJuPxeBwONzIy0tHRMTw8vFY2EIfDAYPl0tISbCuan58nEoloqZaWlkZGRkZGRuAdCQQCmUwmEomTk5Nzc3M4HA6LxY6NjWEwGBwONzs7C1HvmZmZ4eFhiCNBjldXV1dvby/k+Y6NjQ0NDUGSGbzXwsLCwMAArAWurKy0t7e3tbWRSCSIzS4vL2/muYPnODQ0hMFgBgYGoOSwhay+vh7iVB9fRafTKRTKxMTE4OAgBoOZnJzE4XCtra0dHR3d3d0jIyPwsTY0D1QqdWBgoKampra2Fh7a0tIyOzs7Pj5eV1cHQsBQsOnp6fb2djT7fl1zgm/X1NQUFRUVHBxcUFDQ0dFBJpPn5+dTU1PDwsIaGhr6+vra29uHh4eXl5fb2tqampra29sh1j0/P9/e3t7Q0DA0NIRO6Lu6umRkZLZY6F7bbEpLS588eRIfH5+ent7Y2Dg1NVVRUZGZmVlaWjo2NrawsJCfn5+SklJaWorW/+joaFpaWkRERHx8fH5+PliCrq6up0+fJiYmtre3oxHjysrKkJCQ0tLSDWOJgN7e3tjY2OjoaBhkJycnU1NT7969e+fOnefPn09OTm7mzYCz39/fHx0draura2lpmZKSMjEx0dfXFxcX5+7unpyc3N3d3dDQ8PDhw+Dg4MbGRiqVOjg4GBUV9eLFCwqF8vLly7Nnz164cMHExMTd3T0zMxMqjUql5ufnBwUFBQUF1dfXr66uzs/Ph4WFaWlp2djYBAUF1dXVrW0VBQUFAQEBWwe+4C26u7stLS01NTVfvHjx9u3b2NhY2EK8Iaqrqx0dHU1MTGxtbR8/ftzU1AQ3GRsbu3//vrGxsZGRka+vL2QvrKullZWV8vJyc3NzsHyJiYl4PD49PV1cXNzV1bWqqqq0tBTqhEQiBQYGurm5xcfHz87Otre3BwUFPXz4sLy8fGFhob6+3s7OzsjIyNzcPC4uDmZ4/f39np6eSkpKZmZm6enpJSUlDx48KC0t3XqlgEajdXR0hIaGBgUF1dTUbBh/glqdnJx0c3NTVlZ2dnYuKChIT0/39vYeGRlJTEzU09NLS0uD3QNzc3NJSUne3t45OTlxcXFubm6hoaHt7e1AEmZmZqajo1NVVTU+Pm5lZeXs7LyFdwWTEz09PUtLS2traw8Pj4GBATqdXlhY6OXl9fDhQ9Dv3uLLjo6O3rlzR0FBAWY4qamp6Pf6JP75ho3xd2x9zmcd3+y0Lc5fV4yhoaGDBw+iNH0IgnR2dlpZWRUUFGzzoevuvM0SftZPn/Xc7ZRhO+dvZtg+ecPfcMJnnfbbrl17wsrKCoFAWDs0QEbO1pd/fJBKpb5588bBwWELW7IOBAIBi8WC7WcwGBALRRAEXDESiYS6U2vdLywWOz09DSWE8BdE8MCnQd8O5u6bOWRoLIhAIKAXrq6uDg0NDQwMbL2vDC3M8vJye3t7V1cXDLvLy8sEAoFIJIKLtrS0BDuqoHpXV1dJJBKw/zQ1NWlqarq6unZ0dAwODqLeD/idcBWRSITRdmFhob29vb6+/uPEyjt37iQnJ2+tEIZ+64mJic7OTqg3Eom0BR86hUIZHBysra2tr69fl0KAw+Gam5s/fPiwNYfA2NhYc3NzXV0dWIKlpaWOjg5IsUIQBKpoZWVleHgY/NHl5WVw3Ofn53E4HLz42NhYQ0NDQ0PD5OQkGlXG4/F